Transcriptomic analysis reveals distinct mechanisms of carvone and lipopeptide crude extract from Bacillus velezensis JZ in the postharvest biocontrol of Alternaria alternata on strawberries - Lizhu Shao; Boyuan Zhang; Xueling Zhao; Yating Wang; Ziyu Wang; Miaomiao Yang; Zunzun Qi; Yuansen Hu; Na Liu; Peng Li; Li Zhang (Postharvest Biology and Technology, 2027)

Seasonal plant-microbial coupling regulates carbon transformation pathways and soil organic carbon persistence in alpine grasslands - Na Li; Yalin Wang; Shanshan Li; Tianwei Xu; Lin Wei; Shixiao Xu; Na Zhao (CATENA, 2026)

Road surface erosion in a Loess Plateau watershed: Roles of road conditions, upslope contributing areas, and hydrological connectivity - Mengmeng Li; Juying Jiao; Qian Xu; Xiqin Yan; Ziqi Zhang; Jun Liao; Zeng Yan; Wenting Zhao; Xiaohan Jiang; Na Deng (CATENA, 2026)

ROS signaling mediates aeration-dependent thermotolerance in Kluyveromyces marxianus for high-temperature xylitol production - Zhongmei Hu; Yanjie Li; Na Dong; Mingtao Zhao; Bingyi Gao; Juncheng Zhao; Xiurong Tao; Lili Ren; Biao Zhang (Bioresource Technology, 2026)

Icaritin improves pregnancy outcomes in endometriosis by inhibiting ovarian granulosa cell senescence - Yalun He; Jie Ding; Yangshuo Li; Ji Sun; Cuiping Wei; Na Sun; Runnan Jiang; Ziming Zhao; Xiaolan Liang; Yiming Chen; Wen Cheng; Litai Zhang; et al. (Molecular Biology Reports, 2026)

High molecular weight fucosylated glycosaminoglycan promotes the binding of antithrombin and thrombin: a template mechanism and structure-activity relationship study - Chuang Xiao; Li Xu; Ying Cai; Zhenhua Liu; Yingnian Li; Na Gao; Jinhua Zhao (Glycoconjugate Journal, 2026)

XsiAMT1.1a was identified as a novel ammonium uptake functional gene and its overexpression combined with GA4 application significantly increased yield in Arabidopsis thaliana - Xiao Han; Zhao-Hua Gong; Jie Cao; Li-Na Ye; Yuan Cheng; Yu-Xuan Du; Ting-Ting Zhao; Hai-Long Wu; Chang Zhang (Plant Science, 2026)

Columnar optical properties of locally emitted light-absorbing carbonaceous aerosols - Kang Hu; Hong Liao; Dantong Liu; Jianbing Jin; Siyuan Li; Yangzhou Wu; Yuxing Gao; Xiaotong Jiang; Shitong Zhao; Ping Tian; Fei Wang; Na Kang; et al. (Journal of Environmental Sciences, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Long-term nutrient enrichment constrains root exudate-induced priming effects across soil depths in a subtropical forest - Jing Zhou; Jie Li; Na Qiao; Guang Zhao; Xingliang Xu (Applied Soil Ecology, 2026)

Fe(II)-driven abiotic-biotic relay alleviates denitrification bottleneck via chemical nitrite reduction and intracellular carbon - Na Hu; Qi Feng; Chenxi Li; Yuanyuan Liu; Baoli Zhu; Tianci Guo; Lei Tong; Jianbo Shi; Robert A. Sanford; Shuyi Li; Yu He; Yidan Hu; et al. (Water Research, 2026)

Temporal variation in secondary metabolites and antioxidant activity during the biotransformation of American ginseng by Monascus purpureus MN 001: Molecular docking analysis of β-glucosidase-mediated ginsenoside hydrolysis - Li Zhang; Zirui Liu; Boyuan Zhang; Miaomiao Yang; Xueling Zhao; Siliang Lyu; Jiahao Bai; Siyuan Bai; Na Liu; Zhongke Sun; Peng Li; Chengwei Li; et al. (Food Bioscience, 2026)

The dynamic complexity of critical mineral supply chains reveals the paradox of energy transition - Junhui Li; Yongguang Zhu; Shiquan Dou; Qian Zhang; Saleem H. Ali; Gang Liu; Yanqiong Zhao; Na Zhou; Jinhua Cheng; Deyi Xu (Ecological Economics, 2026)

A triboelectric sensor array based on facial muscle-action unit-emotion mapping toward astronaut psychological monitoring in long-term missions - Xuyan Hou; Huiyuan Jing; Meiyang Zhang; Fengyan Liu; Ruiwen Zhao; Zhonglai Na; Pingting Zhao; Yuhui Liu; Ximing Zhao; Linbo Xin; Jian Zhou; Xi Chen; et al. (Chemical Engineering Journal, 2026)

Amino-engineered interfacial photocatalytic membrane with enhanced antifouling and self-cleaning performance for sustainable water purification - Qiaozhi Wang; Qi Zhang; Na Qi; Yehao Yan; Yan Zhang; Ensheng Xu; Hong Chen; Ziyi Wu; Zehui Zhao; Dan Huang; Qingwang Xue; Ying Li; et al. (Chemical Engineering Journal, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Corrigendum to “Fermented Chinese herbal medicines combined with probiotics promote growth of fattening lambs under heat stress by modulating rumen mucosal barrier functions” [Anim. Feed Sci. Technol. 326 (2025) 116384] - Shoupei Zhao; Xinsheng Sun; Na Zhao; Hongwei Zhang; Gaofu Wang; Lu Zhang; Yuqing Liu; Haitong Yang; Jianjie Li; Jia Zhou; Yuhong Gao (Animal Feed Science and Technology, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Phenylbutene dimers and saturated phenylbutene derivatives from Zingiber montanum with anti-inflammatory potential - Zhi-hang Wu; Lu Chen; Jin-na Zhao; Lv-you Wan; Fa-xiang Guo; Lei Zhang; Li-bo Wang; Jin-hui Wang; Xian-mei Piao (Phytochemistry, 2026)

Mg/Ca ratio-regulated phase differentiation of microbially derived CaCO3 and its effects on Cu2+, Cd2+, and Pb2+ immobilization - Kaiming Hu; Yanyang Zhao; Yishui Han; Zuozhen Han; Ruirui Meng; Xiao Gao; Jie Li; Na Guo (Journal of Hazardous Materials, 2026)

Environment and human-health related rodent acute oral toxicity assessment of aniline compounds and their derivatives using QSTR and q-RASTR-based new approach methodologies - Jinxu Li; Shuo Chen; Tengjiao Fan; Ting Ren; Na Zhang; Lijiao Zhao; Rugang Zhong; Zhirong Sun; Guohui Sun (Journal of Hazardous Materials, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

Unraveling the cholesterol-lowering mechanism of a Lactobacillus rhamnosus S_82 and xylo-oligosaccharides synbiotic in sour cream - Xuemeng Fu; Wenhao Zhao; Dongyao Li; Na Zhang; Miaoshu Wang; Xia Tang; Qinghai Sheng; Hongtao Tian; Chen Li (Food Microbiology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Polystyrene microplastic exposure induces hepatic damage via immune-modulated autophagy and ferroptosis in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Xiaolong Fan; Xiaomeng Guo; Na Guo; Tian Gao; Changle Zhao; Yuanyuan Li; Haiyan Xu; Fan Bai; Yixin Chen; Deshou Wang; Lina Sun; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Enhanced hydrothermal stability of Cu-SSZ-13 zeolite catalyst in NH3-SCR via surface-deposited CeO2 nanoparticles - Hui Wu; Na Zhao; Jiarong Li; Yu Wang; Aiping Jia; Ji-Qing Lu (Chemical Engineering Journal, 2026)

One-dimensional chain structure enables anisotropic hard X-ray detection in Hg2Br2 single crystal with ultralow detection limit - Lin Liu; Yunqiu Hua; Qi Li; Tao Wang; Na Lin; Zhongjie Yue; Jian Song; Zhitai Jia; Xian Zhao; Guodong Zhang; Xutang Tao (Chemical Engineering Journal, 2026)

Effects of short-term continuous cropping on soil environmental factors and microbial communities of Pinellia ternata (Thunb.) Breit. - Guoli Wang; Yijia Zhao; Na Liu; Yu Tong; Wen Yin; Pan Li; Chunyu He; Yao Guo (Plant and Soil, 2026)

Differential priming effects induced by leaf- and root-litter in subtropical Chinese fir soil - Jing Zhou; Jie Li; Na Qiao; Guang Zhao; Xingliang Xu (Plant and Soil, 2026)

Dietary Bacillus sp. ‌Modulates Multi-tissue Metabolism Through Gut Microbiota Remodeling in High-fat Fed Larimichthys crocea - Ruojing Li; Biao Yuan; Xin Yi; Ermei Yin; Bi Huang; Qianwen Min; Jiayu Zhou; Meiqi Lv; Bo Zhang; Na Zhao (Probiotics and Antimicrobial Proteins, 2026)

Intracranial EEG reveals working memory-related dynamics and connectivity in human white matter - Shen Zhang; Peng-Hu Wei; Longzhou Xu; Chao Zhang; Na Ao; Haoshu Xu; Yanfeng Yang; Lirou Tan; Zhilin Li; Yali Huang; Jin Li; Jing Liu; et al. (Science Bulletin, 2026)

Data-driven event-triggered fault-tolerant control for offshore floating platforms with improved temporal causal convolutional fault estimation - Wenfeng Li; Qiancheng Dai; Jingang Dong; Pak Kin Wong; Yingbo Huang; Jing Na; Jing Zhao (Ocean Engineering, 2026)

Association of single and combined metal burdens with systemic immune inflammation in smelter workers: A population-based study - Di Wu; Yuankai Cheng; Shuxian Wang; Na Wang; Danhua Zhang; Zhaoyan Wang; Jianxia Cao; Yuzheng Li; Yanhong Li; Jinrui Ma; Yingzheng Zhao; Sihua Wang (Journal of Trace Elements in Medicine and Biology, 2026)

Europium-labeled polystyrene tracing reveals earthworm-mediated inhibition of root uptake and reduced phytotoxicity in lettuce - Nan Chang; Shiqi Bian; Qingliang Cui; Shuling Zhao; Tianyi Qiu; Li Chen; Tao Li; Peng-yang Wang; Roland Bol; Na Wang; Zhiqin Zhang; Fengyu Huang; et al. (Journal of Hazardous Materials, 2026)

Fe/N Co-doped sludge-derived biochar enables rapid Maduramicin adsorption via coupled hydrophobic partitioning and Fe–N complexation - Xinying Li; Huilin Wan; Zhifu Tian; Min Ji; Siyuan Zhai; Qinghua Ouyang; Na Lin; Yingxin Zhao (Journal of Environmental Chemical Engineering, 2026)

A comparative bioprocess for nutrient reclamation: Suspended versus immobilized Virgibacillus salexigens XYD drives struvite recovery from eutrophic saline water - Na Guo; Yueming Zhao; Shuqi Wang; Yanhong Zhao; Yudong Xu; Memon Kashif Ali; Huaxiao Yan; Hui Zhao; Zuozhen Han; Maurice E. Tucker; Chao Han; Yanyang Zhao; et al. (Journal of Environmental Management, 2026)

Simultaneous enantioselective determination of 30 chiral pesticides in vegetables: enantiomeric composition, separation, and absolute quantification using LC-MS/MS - Tianyue Zhao; Xin Jiang; Yingjie Zhu; Danning Shen; Chunzheng Li; Danli Liu; Hui Li; Yanqing Cao; Kun He; Na Wang (Food Chemistry, 2026)

Aldo/keto reductase regulates L-lactate dehydrogenase activity as a key target for yogurt post-acidification - Qingqing Mu; Sitong Jia; Dongyao Li; Whenhao Zhao; Na Zhang; Miaoshu Wang; Hongtao Tian; Chen Li (Food Microbiology, 2026)

The abiotic drivers of soil system perturbation by metallic nanomaterials: a critical review bridging interfacial processes to environmental risks - Mengcheng Zhang; Xue Li; Yongchao Zhao; De'an Chen; Na Tian; Wenrui Zhang; Dongle Cheng; Guang Yang; Xiaoqiang Cao; Yanlong Wang; Huaqing Liu; Jian Zhang (Environmental Research, 2026)

Lignin-nanoparticle/polyethyleneimine nano-assembled membrane with excellent dye/salt separation performance under high salt concentrations - Na Zhang; Ziyi Yang; Xiaotong Lu; Yadi Cai; Jiahui Tian; Saisai Li; Li Zhao; Shuyun Zheng; Hussein Baqiah (Chemical Engineering Journal, 2026)

Secondary disinfection strategies regulate chemical risk and microbial community assembly in secondary water supply systems - Sha Feng; Xing Li; Yongwang Liu; Zedong Lu; Na Li; Yuanrong Qiu; Li Zhao (Chemical Engineering Journal, 2026)

Microalgae-mediated removal and biodegradation of indoor volatile organic compounds: mechanisms, performance metrics, and engineering constraints - Na Li; Can Wang; Jin Zhang; Jing Zhang; Yuanfan Zhao (Biodegradation, 2026)

Study on the Effects of Feeding and Starvation on the External Morphology and Gonadal Development of Artificially Matured American Eel - Lan Wang; Jialun Liu; Zhongmei Yang; Tongxi Ai; Feng Zhao; Keji Jiang; Lei Gao; Mingfei Li; Ye Ding; Na Zhao; Wei Jiang; Xinhui Wei; et al. (Fishes, 2026)
The aim of this study is to investigate how external nutrient supply affects the allocation of reproductive energy during artificial ripening of American eels (Anguilla rostrata), as well as the physiological regulatory mechanisms involved in their bodies. Healthy female American eels were selected for the experiment and randomly divided into two groups: feeding group and starvation group (simulating the natural migration of American eels without eating). The initial weight of the feeding group was (308.43 ± 36.99 g), and the initial weight of the starvation group was (291.67 ± 63.31 g). The entire experiment was divided into two stages: the first stage was a 6-month nutritional reinforcement period, during which the feeding group was regularly fed with Vannamei shrimp, while the starvation group was not fed throughout the entire process. The second stage was a 3-month artificial ripening stage, during which both groups of eels stopped feeding. Inject 1 mL of mixed hormone (containing 6.5 mg of carp pituitary extract CPE+200 IU human chorionic gonadotropin HCG per mL per week) into each eel for a total of 12 injections to induce gonadal maturation. Both groups of eels did not die during the experiment, with a survival rate of 100%. As the gonads continue to develop and mature, the growth and development advantages of the feeding group of eels are very obvious: body weight, chest circumference, and gonadal index are significantly higher than those of the starvation group. After completing 12 hormone injections, the gonadal index of the feeding group reached (32.72 ± 7.01%), while that of the starvation group was only (4.35 ± 2.48%). Under artificial ripening conditions, the egg diameter of the feeding-eel group increased rapidly in the later stage of the experiment. The growth rate of eggs in the starvation group was slow, and the final egg diameter was significantly smaller. The diameters of the nuclei of both groups of oocytes increased synchronously with the progress of the experiment; the number of nucleoli in the feeding group first increased and then decreased, while the number of nucleoli in the starvation group continued to increase. The oil droplets inside both sets of eggs gradually increased in size, and the oil droplets fed to the eggs in the middle and late stages of maturation had a larger volume. Hormone test results showed that the testosterone (T) level in the eel fed group increased significantly in the later stage of the experiment. This indicates that adequate nutrition can alleviate the inhibition of the reproductive endocrine axis through positive feedback regulation of the pituitary gonad (BPG) axis. Nutritional reinforcement before ripening can promote gonadal development and enhance reproductive capacity by regulating the distribution of nutrients between muscles and gonads. The results of this study provide a solid theoretical basis for improving the nutritional management plan for parent fish in the fully artificial breeding process of American eels.

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

From morphological constraints to genomic SNPs: Developing population identification methods exemplified by large yellow croaker (Larimichthys crocea) - Zebin Zhou; Xubing Ba; Qianwen Min; Jiayu Zhou; Xin Yi; Ruojing Li; Bi Huang; Na Zhao; Bo Zhang; Songlin Chen (Aquaculture, 2026)

Persistent testicular glycogenolysis and active lipid metabolism during torpor in hibernating Siberian chipmunks - Zhe Wang; Lu-Fan Li; Yu-Jing Yan; Ming-Yan Yuan; Xiang-Yu Zhao; Li-Na Jiang; Xian-Feng Yi (Journal of Thermal Biology, 2026)

Aggregation-disaggregation cycling: A physical strategy for low-viscosity fish protein particles - Xueer Yu; Xinyao Zhao; Bowen Zou; Aijun Jian; Jiaxin Li; Xianbing Xu; Ming Du; Chao Wu; Xiaokang Na (Food Chemistry, 2026)

Decoding the neural mechanisms of salty peptide perception via electroencephalography and machine learning - Xuchao Feng; Hongbo Li; Quanyu Dai; Na Li; Lili Zhao; Zhenbin Liu; Jiayi Zhang; Haizhen Mo (Food Chemistry, 2026)

Selenomethionine antagonizes sodium arsenite-induced reproductive toxicity in zebrafish - Yan Zhang; Huan Wang; Xinru Bo; Yangfan Xu; Lingtian Xie; Yunyang Li; Jingli Mu; Jialing He; Na Zheng; Baoquan Zhao; Hongxing Chen; Wu Dong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Ultrahigh energy storage density under a low electric field in Sm-modified lead-free high-entropy perovskite ceramics - Chengyou Wang; Jiangnan Hu; Li Wang; Chong Zhao; Na Tu; Xin Nie; Dongxu Li; Chao Chen; Xiaokun Huang; Xiangping Jiang (Chemical Engineering Journal, 2026)

Correction to: Cardioprotective effects of notoginsenoside R1 on myocardial remodeling and cardiac function in restraint stress‑induced MI in rats - Peng Sun; Cuiyu Han; Qian Sun; Tingting Li; Lan Li; Mingxing Shi; Pei Zhao; Lu Chen; Na Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effects of PE microplastics on root morphology and soil nutrients with mechanisms of rhizosphere enrichment in Brassica rapa var. chinensis - Yifei Lin; Chenrui Zhao; Chengliang Li; Lei Hou; Na Liu; Yicheng Fu; Qian Zhang (Journal of Soils and Sediments, 2026)

A one-tube RAA-PfAgo system for rapid and sensitive detection of Monkeypox virus - Na Zhao; Xuejian Zhang; Yulu Gan; Lin Li; Yunmin Wang; Tong Xu; Yao Pan; Kui Gu; Yu Zhao (Analytica Chimica Acta, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

An integrated assessment of water and carbon footprints with energy evaluation in the cinnamon soil region of Northeast China - Yidong Zhao; Baoqing Chen; Yisheng Lou; Na Li; Lu Hua; Hongyan Gao; Qian Cai; Wei Bai; Wenyi Dong; Zhe Zhang (Environment, Development and Sustainability, 2026)

PPAOT predictor: ARKA-RASTR strategy-driven rodent acute oral toxicity prediction for pyrazole and pyrrolidine scaffolds-based chemicals with intelligent mechanistic interpretation - Jianing Xu; Shuo Chen; Ting Ren; Feifan Li; Na Zhang; Lijiao Zhao; Rugang Zhong; Guohui Sun (Archives of Toxicology, 2026)

Fe3O4-doped DCD-modified PAN-based nanofiber mat with synergistic photo-Fenton catalytic evaporation performance for multifaceted water treatment - Yifan Niu; Wenxin Wang; Mingzhe Zhao; Ning Wang; Martin Jensen; Na Han; Xianfeng Li (Journal of Environmental Chemical Engineering, 2026)

Continuous plastic film mulching reduces global warming potential (GWP) in greenhouse soil biosolarization by regulating microbial carbon and nitrogen metabolism - Qianru Liu; Qiang Zuo; Yuteng Qi; Yufan Yang; Guochun Ding; Mao Li; Guicheng Han; Yinzhi Chu; Bingxue Wang; Yuhao Sun; Xiao Zhao; Lianfeng Du; et al. (Journal of Cleaner Production, 2026)

An active cling film developed from pomelo peel for synergistic preservation of Oncorhynchus mykiss: Utilizing K/Fe enzyme-like materials and natural extracts - Tao Yu; Long Cheng; Yini Zhao; Long Gu; Hangfei Gao; Zicen Liu; Li Huang; Shuyan Bai; Dongli Qin; Peng Wang; Aimin Wang; Haijiao Xie; et al. (Food Packaging and Shelf Life, 2026)

Plastisphere as an eco-site for horizontal gene transfer: Enhancing antibiotic resistance in marine biofilms - Chaoran Li; Zhihang Chen; Hongyi Chen; Zhonglai Zhou; Lingchen Zhang; Lina Zhao; Hui Zhong; Na Wang (Environmental Research, 2026)

Source contact engineered high-gain and low-power Schottky-barrier transistors for electrophysiological amplification - Biao Zhou; Linjing Wang; Chenchen Wei; Jietao Zhuo; Na Liao; Wei Zhou; Huihua Xu; Fengyu Li; Zhao Dong (Chemical Engineering Journal, 2026)

Characterization of a new diterpenoid glycoside and chemotaxonomical significance of secondary metabolites from Excoecaria acerifolia - Na-Li Song; Jia-Peng Wang; Li-Ping Yang; Sheng-Qi Zhang; Xia Zhao; Le Cai; Zhong-Tao Ding (Biochemical Systematics and Ecology, 2026)

Time-dependent biphasic dysregulation of autophagy and innate immunity underlies polystyrene microplastics-induced hepatotoxicity in Nile tilapia - Feilong Wang; Xiaomeng Guo; Na Guo; Xiaolong Fan; Haiyan Xu; Yuanyuan Li; Tian Gao; Yixin Chen; Changle Zhao; Lina Sun; Deshou Wang; Xin Xie; et al. (Aquatic Toxicology, 2026)

Single-cell profiling and machine learning identify cuproptosis-related fibroblast subpopulations and fibrogenesis modulator AEBP1 in endometriosis - Erqing Huang; Jiang-Tian Li; Danhui Zuo; Ruijie Li; Qingyue Wu; Na Lin; Jinru Zhao; Huajing Wang; Yi Liu; Ling Zhang (Apoptosis, 2026)

The major chemical constituents of Penthorum chinense Pursh and their inhibitory activity against enzymes associated with metabolic dysfunction-associated steatotic liver disease - Chao-Qun Wang; Meng-Qi Wang; Xiao-Na Gan; Ting-Zhao Li; Xiang-Wei Zheng; Bo Li; Xin Fang; Shuang Liang (Natural Product Research, 2026)

The interaction between DNA methylation and single-nucleotide polymorphism in regulating the mRNA expression of CYP1A1, GSTP1 and GSTM1 in population - Aixiang Liu; Yuxin Shi; Xin Li; Miao Wu; Tingyi Zhao; Yingying Wu; Na Xia; Hongmei Zhang (Toxicology Letters, 2026)

Benzo[a]pyrene lowers the sperm quality in male rats by downregulating the expression of ZMYND15 and ZMYND10 - Xinrui Zhao; Xiuxia Dong; Pengjuan Fu; Yongkang Chen; Na Liu; Bohe Wang; Xiaojuan Feng; Xiangli Li (Reproductive Toxicology, 2026)

A novel natural thermal-cooling cycle treatment for hemp fibers degumming - Yu-Pu Fan; Wen-Na Xu; Ming-Hui Wang; Xin-Hui Zhao; Zhi-Gang Li (Journal of Cleaner Production, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

A review of pentacyclic triterpenoids derived from macrofungi and their biological activities - Zhiyuan Jia; Yuying Liu; Tong Zhang; Zhenxin Wang; Ling Zhao; Na Zhang; Haiqiang Wang; Vadim Khassanov; Zhenpeng Gao; Can Du; Minglei Li; Jianzhao Qi (Food Bioscience, 2026)

A food-grade antimicrobial peptide from Lactococcus lactis: A potent and stable bio-preservative against Gram-negative pathogens in orange juice - Mingyang Hu; Sina Cha; Yuwen Li; Lu Zhao; Yutong Xue; Chenyu Xue; Na Dong; Anshan Shan (Food Control, 2026)

Key enzymes in N6-methyladenosine modification regulate plant stress tolerance by modulating mRNA stability - Zishuo Han; Hongxiang Zheng; Yinping Gao; Simin Li; Zengting Chen; Fangning Zhang; Fenghui Wu; Zhiying Zhao; Lei Yan; Na Sui (Plant Cell Reports, 2026)

Spatiotemporal distribution and host association of antibiotic resistance genes in sediment of Qiantang river basin - Qiannan Jin; Jie Li; Yantan Zhou; Guangqian Zhao; Yuhan Jiang; Na Cheng; Lifang Hu (Environmental Geochemistry and Health, 2026)

Activating FcγRI inhibits RIG-I-mediated host antiviral innate immunity by FGR during PRRSV-ADE infection - Peng-li Xu; Yi-han Li; Fa-hao Li; Shi-jie Zhao; Wen Li; Jing Chen; Ping-an Xia; Yi-na Zhang (Veterinary Microbiology, 2026)

Seasonal decoupling of water supply and CO2 fluxes of urban greening shrubs is driven by leaf area index - Wenxu Huang; Shaoning Li; Shaowei Lu; Na Zhao; Bin Li; Yuan Niu; Jiaying Li; Xiaotian Xu (Journal of Environmental Management, 2026)

Enhancing Li+ exchange efficiency of lithium slag via alkaline adjustment: Investigation into the multi-cation systems and insights for waste recycling - Na Wang; Jieyu Zhao; Hankun Zhang; Tianlei Wang; Jixue Shen; Qian Kang; Longfeng Tao; Xi Yue; Chuncheng Yang; Hongchao Li; Changjiang Liu (Journal of Environmental Chemical Engineering, 2026)

Asynchronous abrupt changes of lake ecosystems in the Anthropocene - Dinggui Wu; Tian Xia; Qingfeng Zhao; Yibin Sun; Na Song; Man Li; Tianchen He (Global and Planetary Change, 2026)

Effects of Pediococcus pentosaceus and tea polyphenols on biogenic amines, volatile compounds, and microbial Community in Fermented Sausage - Erke Sun; Xueying Sun; Weiqi Qin; Shiqi Hao; Yanrong Chen; Lina Sun; Ye Jin; Na Wang; Rugang Tian; Hui Li; Jie Kang; Xun Xiao; et al. (Food Chemistry, 2026)

Anti-inflammatory activity of quinoa-based protein beverage after INFOGEST digestion: Peptide identification and molecular docking-based screening - Mengzhuo Li; Feng Lu; Liang Zou; Hye-Kyung Na; Junjuan Wang; Pan Wang; Dan Wang; Yuanyan Zhao; Xiaoyan Zhao; Peiyou Qin (Food Chemistry, 2026)

Enhanced metal-organic framework-driven deep learning-assisted magnetic crystal paper aptsensor for two-step sensitization and in-situ detection of pathogenic bacteria - Lulu Cao; Yuwei Ren; Shengshi Jiang; Hui Li; Maoling Hu; Xin Zhang; Xiaoyu Yu; Weichao Wu; Mengyu Li; Zhao Liang; Na Ling; Hongzhou Chen; et al. (Chemical Engineering Journal, 2026)

Mobilization and redistribution of Arsenic during intense weathering of granite, eastern Tibetan Plateau, China - Zi-Han Xia; Jun-Wen Zhang; Na Wu; Mei-Li He; Qi Liu; Zhi-Qi Zhao (Environmental Geochemistry and Health, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Experimental investigation on adiabatic two-phase frictional pressure drop of R290, R600a, and their mixtures in a horizontal minichannel - Na Liu; Hao Ji; Yeyi Liu; Run Li; Dezheng Sun; Qian Zhao; Jianxiang Guo (International Journal of Refrigeration, 2026)

Revisiting global cropland water use efficiency: Insights from satellite remote sensing - Lingxiao Huang; Yizhe Wang; Meng Liu; Na Yao; Yunjun Yao; Zhao-Liang Li (Global and Planetary Change, 2026)

Pressure-driven depolymerization of Antarctic krill aggregates: Structural reconfiguration and gelation-enhanced functionality - Na Li; Qingcheng Meng; Xin Zhao; Fawen Yin; Dayong Zhou; Deyang Li (Food Chemistry, 2026)

Construction of nano-rubber toughened double-network hydrogels and the efficient adsorption performance and mechanism for uranyl ions - Bo Tian; Jianwei Zhang; Wenze Li; Jinfeng Li; Na Zhou; Zhigang Li; Wa Gao; Nan Zhang; Hongtao Zhao (Environmental Research, 2026)

Biomineralization induced by Shigella dysenteriae JS3: The mechanism, and the differences between biotic and abiotic whewellite and struvite - Na Guo; Jizheng Qiao; Shuhua Zhang; Shengzhe Gao; Yanhong Zhao; Chao Han; Hui Zhao; Yanyang Zhao; Xiao Gao; Ruirui Meng; Bin Cao; Yu Li; et al. (Chemical Geology, 2026)

Cardioprotective effects of notoginsenoside R1 on myocardial remodeling and cardiac function in restraint stress-induced MI in rats - Peng Sun; Cuiyu Han; Qian Sun; Tingting Li; Lan Li; Mingxing Shi; Pei Zhao; Lu Chen; Na Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Effects of two-stage illumination strategy on the growth and nutrient composition of Chlorella sp. - Zhujun Qiu; Yuande Zhang; Yuqing Wang; Wenyu Zhao; Chonghui Fan; Yao Zhang; Ziyi Sun; Na Li; Qian Zhang (Algal Research, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

Millennial- to centennial-scale record of organic carbon accumulation and its periodic occurrence in the Yellow Sea since the last deglaciation - Yuying Zhang; Limin Hu; Yazhi Bai; Lina Jin; Hyung Jeek Kim; Na Li; Song Zhao; Jun Ye; Yonghua Wu; Xiao Wu; Xiting Liu; Xun Gong; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Synthesis of amidoxime functionalized hydrogel for in-situ toughening and adsorption of uranium - Bo Tian; Jianwei Zhang; Jinfeng Li; Na Zhou; Wenze Li; Wa Gao; Nan Zhang; Hongtao Zhao (Journal of Environmental Chemical Engineering, 2026)

Study on mechanical properties of non-diagenetic hydrates-bearing sediments under in-situ static conditions - Na Wei; Jiang Wu; Haitao Li; Jun Pei; Shouwei Zhou; Jinzhou Zhao; Bjørn Kvamme; Richard Banks Coffin; Anping Feng; Jianyong Feng (Fuel, 2026)

Integrative metabolomics-assisted comprehensive components analysis of complex system (CCACS) revealed functional potential: Valorization of gourd fruit (Trichosanthes kirilowii maxim.) - Wen Miao; Na Li; Lanjia Ao; Yujie Li; Ying Liu; Yiran Zhao; Xiaolin Chen; Yuyao Wu; Jian-Lin Wu (Food Research International, 2026)

Self-driven degradation and protection against chemical warfare agent simulants via MOF-808 derived bipolar membrane interfaces - Na Gao; Xiao-Peng Li; Xinbo Wang; Li Li; Heguo Li; Fen Luo; Yue Zhao; Huan Xu; Liang Wu (Chemical Engineering Journal, 2026)

Pectic polysaccharides from Mongolian medicinal Hypecoum leptocarpum: Structure and ulcerative colitis amelioration via gut microbiota and intestinal inflammation regulation - Cunwuliji Na; Xiang Shi; Jicheng Fu; Jiahao Li; Hongyu Jiang; Zhiwei Guo; Hongyan Lai; Zhipeng Zhang; Longyan Zhao; Qingxia Yuan; Baoshun Zhang (Carbohydrate Polymers, 2026)

CCT7 predicts poor prognosis and correlates with immune infiltration in colonic adenocarcinoma - Wenxu Li; Qizhong Shi; Yonghui Mu; Chenglei Li; Wenchao Zhao; Na Han (Journal of Molecular Histology, 2026)
CCT7, a member of the t-complex polypeptide 1 chaperone family, facilitates ATP-dependent protein folding; however, its role in development and progression of malignant tumors remains unclear. This study aimed to characterize the expression pattern of CCT7 in colonic adenocarcinoma (COAD) and evaluate its role in the initiation and development of COAD. Public bioinformatic databases were analyzed to assess CCT7 expression in COAD, and these findings were validated using human clinical specimens through immunohistochemistry (IHC) assay. The prognostic significance of CCT7 was examined using Kaplan–Meier method and Cox regression analysis. Gene Ontology-Biological Process (GO-BP) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to explore the potential biological functions and downstream pathways associated with CCT7. CCK-8, colony formation and Transwell assays were conducted to determine the impact of CCT7 on cell proliferation, migration and invasion in COAD cell lines. Associations between CCT7 expression and immune cell infiltration or drug sensitivity were evaluated using single-sample gene set enrichment analysis and correlation analysis. Finally, immune checkpoint inhibitor therapy scores and their relationship with CCT7 expression were assessed using data from The Cancer Immunome Atlas. CCT7 expression was significantly up-regulated statistically in COAD tissues compared with normal colonic tissues ( P < 0.05) and elevated CCT7 levels were associated with poorer prognosis of COAD patients ( P < 0.05). GO-BP enrichment analysis indicated that CCT7 was primarily involved in the processes related to cell proliferation and microtubule organization ( P < 0.05). Consistently, functional assays confirmed that CCT7 knockdown inhibited COAD cell proliferation, migration, and invasion ( P < 0.05). CCT7 expression showed a negative correlation with infiltration of most immune cell types ( P < 0.05) and demonstrated no significant association with predicted responses to PD-1 and CTLA-4 inhibitor therapies ( P > 0.05). Moreover, drug sensitivity analyses showed that CCT7 affected the sensitivity of COAD samples to several anti-cancer drugs ( P < 0.001). KEGG enrichment analysis revealed that CCT7 was associated with multiple pathways ( P < 0.05). CCT7 may function as an oncogenic driver that promotes the malignant phenotype of COAD and represents a promising prognostic biomarker. It may also provide a valuable reference for guiding clinical therapeutic strategies in COAD.

Contrasting temperature responses of photosynthesis and respiration amplify reduction in carbon sink under water stress conditions in a temperate semi-arid steppe - Xinhao Li; Tianshan Zha; Peng Liu; Xin Jia; Yun Tian; Hongxian Zhao; Jinshi Jian; Na Deng (Agricultural and Forest Meteorology, 2026)

Three-dimensional suspension induction of porcine EPSCs into PGCs - Liming Yuan; Xiaolong Wu; Xiaoxiao Fu; Zuo Lei; Hongzhao Shi; Wenjie Xu; Yaya Zhao; Jiannan Li; Xueting Li; Lexi Gao; Na Li; Jinlian Hua (Theriogenology, 2026)

Mutant transcription factor CopR promotes LDB_RS05285 expression to suppress yogurt post-acidification and enhance texture stability - Wenhao Zhao; Xuemeng Fu; Dongyao Li; Qingqing Mu; Na Zhang; Yongsheng Sun; Miaoshu Wang; Hongtao Tian; Chen Li (Food Research International, 2026)

Advanced physical-based techniques for the extraction and modification of plant protein: mechanisms, functions, and applications - Yi-han Cai; Meng-na Li; Hao-yue Xu; Fang Huang; Yu-xin Zhao; Jie-han Zhang; Yan-yan Huang; Xin-An Zeng (Food Chemistry, 2026)

Transcriptomics, 16S rDNA, and metabolomics reveal Alhagi honey polysaccharides alleviating alcoholic liver disease via gut-liver axis - Jianzhong Song; Xin Zhao; Zhiyuan Lv; Jinfa Li; Na Mi; Junmin Chang; Xiumin Ma (Food Bioscience, 2026)

Nutritional regulation by vitamin A: Comprehensive impacts on growth, molting, immunity, lipid metabolism, and ovarian maturation in red swamp crayfish (Procambarus clarkii) - Jiacheng Yu; Siying Hu; Fuxian Zhang; Donglin Cui; Yihan Wu; Runyu Li; Na Li; Chengmin Zhao; Kai Luo; Weihua Gao; Shouqi Xie (Fish & Shellfish Immunology, 2026)

Span80 induced orderly diffusion of monomer for the construction of small pore volume polyamide nanofiltration membrane with high Li/Mg separation ratio - Lu Gao; Yue Miao; Xiaowen Huo; Yingying Zhao; Zhaojing Jing; Xiuling Liu; Haitao Wang; Ning Fan; Qiuying Jia; Kai Ren; Jun Li; Na Chang (Desalination, 2026)

Scalable wet-spun stretchable conductive fibers with SWCNT-enhanced mechanical and electrical properties for multifunctional wearables - Xu Zhao; Zirong Luo; Tuanzhang Li; Wenfa Mao; Fangting Mo; Yanqiu Shao; Shuang Li; Jizhen Zhang; Na Kong; Jihua Li; Jinlong Tao (Chemical Engineering Journal, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Hepatic cyp24a1 serves as a biomarker for diagnosing polystyrene microplastic exposure in Nile tilapia (Oreochromis niloticus) - Feilong Wang; Haiyan Xu; Xiaomeng Guo; Xiaolong Fan; Yuanyuan Li; Tiao Gao; Xin Xie; Na Guo; Fan Bai; Yixin Chen; Changle Zhao; Deshou Wang; et al. (Aquatic Toxicology, 2026)

Production and Functional Evaluation of Recombinant Active Peptide RH in Pichia Pastoris: Protection Against Escherichia Coli Induced Cell Death - Lu Zhao; Mingyang Hu; Yuwen Li; Jiaoyu Xin; Yuxin Fang; Chenyu Xue; Na Dong (Probiotics and Antimicrobial Proteins, 2026)

Cang-Ai Volatile Oil Mitigates Lipopolysaccharide-Induced Depressive-Like Behaviour in Mice by Modulating the Microglial BDNF/CREB Signaling Pathway - Lianna Zhao; Run Yin; Kailing Zhang; Jinqing Huang; Ruiyu Zheng; Youyang Zhu; Gang Li; Na Lei; Lei Xiong; Yuhuan Xie (Molecular Neurobiology, 2026)

miR-133b-3p Mitigates D-Galactose-Induced Hippocampal Neuron Aging Through Autophagy Regulation via the MAPK/ERK Signaling Pathway - Yang Cao; Chen Zhao; Jiaxin Li; Qiang Gao; Chunmei Lv; Jiao Wang; Na Qiang; Wenwen Zhang; Huiyu Su; Xinyu Min; Jinfeng Liu; Xiaoqi Dai; et al. (Molecular Neurobiology, 2026)

Healthy diet and slower biological aging as protective factors against microvascular complications in type 2 diabetes - Han Zhou; Shuai Ben; Qian Ma; RuiKang Yang; Jiao Xia; XiongYi Yang; Jing Li; JunYa Zhu; Qian Liu; Ya Zhao; Na Li; Kun Liu; et al. (GeroScience, 2025)

Cellulose acetoacetate carbanion ion pair organocatalyst in homogenous catalysis of CO2 fixation and heterogenous recycle - Yanqi Shi; Jiahui Ma; Zhenjiang Li; Xin Yuan; Xin Zou; Na Shi; Ziqi Liu; Min Zhang; Hui Zhao; Kai Guo (Sustainable Chemistry and Pharmacy, 2025)

Characterization and risk prioritization of PFAS via nontarget screening in soil and maize near a fluoropolymer manufacturing facility - Xiaotong Li; Na Li; Ru-song Zhao; Yali Shi; Yaqi Cai (Journal of Hazardous Materials, 2025)

Spatiotemporal dynamics and ecological risks of antibiotics and antibiotic resistance genes in a typical tropical river-bay system: Insights from Sanya, China - Xiaodi Zhang; Qing’an Xie; Shisheng Li; Shengkai Cao; Yao Liu; Wei Wang; Junfu Zhao; Guangshui Na (Journal of Environmental Chemical Engineering, 2025)

Enhancement of stability and hydrogel properties of type-A gelatin-dextran mixtures via incorporation of whey protein isolate fibrils - Ling Wu; Die Dong; Zhengzong Wu; Jianpeng Li; Lu Lu; Na Wang; Yisu Yang; Meng Zhao; Bo Cui (Food Research International, 2025)

Dual-signal ratiometric electrochemical aptasensor based on COFs-derived Fe/N-doped porous carbon and methylene blue-enriched COFs for sensitive and accurate detection of kanamycin - Haiyan Zhao; Yunzhi Zhao; Shanshan Li; Meiya Zhang; Na Li; Min Cui; Cong Zhang (Food Chemistry, 2025)

Influence of solid-state fermentation with lactic acid bacteria on the structure, physicochemical and adsorption properties of dietary fiber in rice bran - Dan Wang; Xiao-Tong Zhai; Na-Na Wu; Jun Li; Ming Zhao; Na Zhang; Bin Tan (Food Bioscience, 2025)

Recent advances of multivalent metal nanozymes in analysis and detection - Zhao Li; Weidan Na; Chuangeng Tian; Jianguo Dong; Lin Tian; Ming Ma; Tognxiang Li; Yu Zhang (Chemical Engineering Journal, 2025)

Reversible metal electrodeposition assisting polyaniline for tri-mode adaptive radiative thermoregulation devices - Dongqi Liu; Na Li; Qingchao Fan; Wenchao Liu; Yike Zhang; Lei Xu; Jiupeng Zhao; Leipeng Zhang; Yao Li (Chemical Engineering Journal, 2025)

Quercetin-loaded milk-derived extracellular vesicles for the treatment of inflammatory bowel disease by alleviating senescence-associated cell cycle arrest - Runrun Wan; Tingting Cao; Meng Deng; Chengbiao Hu; Caixiao Liu; Yijuan Han; Na Zhao; Qiaoning Wang; Xueru Li; Xiangdong Wang; Chenghu Hu; Zhang Yuan (Chemical Engineering Journal, 2025)

Genetic structure analysis of a newly discovered wild population of Pontastacus leptodactylus in Xinjiang, China, based on the mitochondrial COI gene - Bin Li; Haorui Wang; Haini Shi; Qi Zhao; Shuxian Li; Adelijiang Wusiman; Maimaiti Aizizi; Ming He; Kefa Zhang; Yang Zhang; Na Li (Molecular Biology Reports, 2025)

Topographic differences in EEG microstates: distinguishing juvenile myoclonic epilepsy from frontal lobe epilepsy - Ying Li; Lidao Xu; Yibo Zhao; Mingxian Meng; Yanan Chen; Bin Wang; Beijia Cui; Jin Liu; Jiuyan Han; Na Wang; Ting Zhao; Lei Sun; et al. (Cognitive Neurodynamics, 2025)

Elucidating the material basis and therapeutic mechanisms of Shaoma Zhijing granules for tourette syndrome by UPLC/Q-TOF-MS and multiple models - Qian Zhao; Xin-Xin Xu; Jin-Na Yang; Li-Juan Pei; Zhou-Yi Xie; Wen-Jia Wang; Jing-Xuan Fu; Zhao-Hui Song; He Sun; Kai-Jing Yan; Hui Wang; Yun-Hui Hu (Metabolic Brain Disease, 2025)

Newly discovered Late Paleolithic sites in the southeastern margin of the Badain Jaran Desert, northwest China - Lu Teng; Xuefeng Sun; Hui Liu; Na Zhao; Shuangwen Yi; Feng Li; Xiaoqi Guo; Yuan Yao; Yinghua Wang; Christopher J. Bae; Huayu Lu (Quaternary Science Reviews, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Enhancement of soil organic matter stability cross-linked with aluminium drove the reallocation of ROSs for the directional oxidation of petroleum hydrocarbons - Xiumin Li; Yonghua Zhao; Hongliang Du; Di Han; Na Wang (Journal of Environmental Management, 2025)

Biomimetic GNPs-interwoven photonic molecularly imprinted polymer for the colored determination of trace 17β-estradiol - Jiayue Zhou; Dongmei Li; Tiantian Li; Ziwei Chen; Zhuxin Chang; Guanggui Yu; Ruicong Zhou; Linyuan Wang; Yinuo Chen; Jie Zhao; Huan Liu; Na Sai (Food Chemistry, 2025)

Effect of ammonium chloride on the salt-induced cohesive behavior of egg yolk liquid and its plasma with granules - Yufei Ye; Hang Li; Na Wu; Shuping Chen; Lilan Xu; Yan Zhao; Yonggang Tu (Food Chemistry, 2025)

Screening of proteins interacting with PirA and PirB from Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease in Pacific white shrimp Litopenaeus vannamei - Li Jiang; Na An; Rong Fan; Dianli Zhao; Mengqiang Wang (Fish & Shellfish Immunology, 2025)

Photoresponsive leaf-like structured two-dimensional metal-organic framework/nanocellulose crystal composites for efficient and rapid adsorption of pollutants from wastewater - Saisai Li; Luying Wang; Juan Dai; Na Zhang; Li Zhao; Shuyun Zheng; Xinxin Li; Caicai Lin; Dashuai Zhang; Qiang Li (Chemical Engineering Journal, 2025)

Investigation of the South Atlantic Anomaly (SAA) by proton flux variabilities based on 6 years’ CSES data - Lu Wang; Zhenxia Zhang; Xinqiao Li; Zhenghua An; Yanbing Xu; Ping Wang; Hong Lu; Xiaoyun Zhao; Dali Zhang; Xiaohua Liang; Zhiqiang Ding; Shujie Li; et al. (Science China Earth Sciences, 2025)

miR-133b regulation of wbp2 in ovaries is conserved among teleosts - Jiayu Zhou; Qianwen Min; Xubing Ba; Zhaoqiu Qu; Zhenjun Zhuang; Biao Yuan; Xin Yi; Ruojing Li; Na Zhao; Bo Zhang (Acta Oceanologica Sinica, 2025)

Molecular interactions of icariin and icariside II with human serum albumin: a spectroscopic and molecular docking analysis - Na Wang; Kang-huai Zhang; Jiao Xie; Li Zhang; Hai-tao Wang; Xin Yang; Yi Zhao (Natural Product Research, 2025)

Microplastic contamination in kidney transplant donor tissues and its association with early post-transplant blood pressure changes in recipients: A multi-modal analytical study - Tianyi Wang; Na Li; Zehao Zhao; Yang Zhang; Li Lin; Yaodong Ding; Ruixiang Feng; Zhe Yang; Wenzhi Du; Yong Zeng (Journal of Hazardous Materials, 2025)

Corrigendum to “Synchronous precipitation of secondary dissolved organic matter promoted ROS transfer to solid phase for enhancing the removal of absorbed petroleum hydrocarbons in soil” [J. Environ. Chem. Eng. 13 (2025) 119034] - Xiumin Li; Hongliang Du; Yonghua Zhao; Yang Zhang; Na Wang (Journal of Environmental Chemical Engineering, 2025)

Synchronous precipitation of secondary dissolved organic matter promoted ROS transfer to solid phase for enhancing the removal of absorbed petroleum hydrocarbons in soil - Xiumin Li; Hongliang Du; Yonghua Zhao; Yang Zhang; Na Wang (Journal of Environmental Chemical Engineering, 2025)

Application of magnetic chitosan gel combined with magnetic solid phase extraction based on deep eutectic solvent for the residue analysis of ofloxacin and enrofloxacin in milk - Wen Li; Yue Na; Wenqi Wang; Yingtong Ma; Ning Liang; Longshan Zhao (Food Chemistry, 2025)

Parallel algorithm of watershed delineation by considering the topological relationship into information organisation - Fei Zhao; Liyang Xiong; Hongen Wang; Lanhua Luo; Jiaming Na; Sijin Li; Guoan Tang (Environmental Modelling & Software, 2025)

Enhancing capacitive deionization with element-doped carbon nanotube electrodes for selective uranium ion removal - Na Liu; Xinhua Huang; Yulin Ye; Hui Li; Ruikun Zhao; Guangzhi Hu (Desalination, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Bufadienolides from Helleborus thibetanus Franch and their chemotaxonomic significance - Fengying Yang; Mengjia Liu; Shan Xie; Rongxian Li; Han Xue; Xianshou Zhao; Wenying Yin; Na Liu (Biochemical Systematics and Ecology, 2025)

Vertical distribution and regional transport of air pollution over Northeast China: Insights from an intensive aircraft study - Ye Shan; Yujiao Zhu; Haoxin Sui; Na Zhao; Hongyong Li; Liang Wen; Tianshu Chen; Yanbin Qi; Wenlong Qi; Xinfeng Wang; Yuqiang Zhang; Likun Xue; et al. (Atmospheric Environment, 2025)

Interspecific interaction with Trifolium repens improved the phytoremediation efficiency of Lolium perenne to Cd contaminated soil by changing microbial community, soil metabolome and improving plant growth - Na Li; Yuke Li; Ronggui Liu; Jiyi Gong; Chao Wang; Kamran Malik; Lanlan Chen; Jing Zhang; Qing Zhao; Ming Zhu Tian; Zhirui Wen; Jianfeng Wang; et al. (Plant and Soil, 2025)

Correction to: Exploring the bioactive ingredients of three traditional Chinese medicine formulas against age-related hearing loss through network pharmacology and experimental validation - Wenying Shi; Qi Zhao; Hongwei Gao; Yaxin Yang; Zhiyong Tan; Na Li; Hongjie Wang; Yonghua Ji; You Zhou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Aporphine alkaloids and flavonoids from the roots of Fissistigma retusum (H. Lév.) Rehder - Ya-Ting Xiao; Xue-Na Zhao; Han Li; Ying Ren; Yu-Hang Liu; Yu-Ming Liu (Natural Product Research, 2025)

UAV-based fine-scale daily relationship characterization between 3D urban surface thermal dynamics and landscape patterns - Rongyuan Dai; Fengxiang Guo; Han Zhao; Linshan Zhong; Chunyu Zhu; Na Ta; Hongqing Li; Qiong Wu (Sustainable Cities and Society, 2025)

Green manure roots return drives saline-alkali soil organic carbon accumulation via microbial necromass formation - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Xiaodong Liu; Jie Zhou; Yuyi Li (Soil and Tillage Research, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Bioelectrochemistry increases the risk of resistance genes proliferation and transfer with sulfamethoxazole pressure decreasing in constructed wetlands: An overlooked double-edged effect - Xin Shan; Hutao Wang; Maozhen Han; Na Zhang; Fengling Zhang; Shaoyong Lu; Bin Zhao; Xiaohui Liu; Fengmin Li; Fengchang Wu (Journal of Hazardous Materials, 2025)

Specific recognition schemes based on structure-activity relationship: Aniline-functionalized carbon dots for the detection of pyrethroids in beef and environment - Jianhang Duan; Chunyang Chen; Hongke Bie; Yuheng Zhao; Kedi Zhao; Na Gu; Jiahang Li; Jin Yan; Wei Liu; Xuedong Wang (Journal of Hazardous Materials, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Constructing nitrogen-doped porous organic polymer- supported single-atom cobalt catalysts for highly efficient hydroformylation of internal olefins - Yuqing Wang; Miao Jiang; Na Liu; Tian Tian; Changdao Li; Zhao Sun; Gewen Yu; Yanming Wang; Wenxiu He; Jian Ding; Li Yan; Yunjie Ding (Chemical Engineering Journal, 2025)

The Role of HbA1c in Parkinson's Disease: An Integrative Analysis by Single-Cell, Bulk Transcriptome and Mendelian Randomization - Huihe Zhang; Wei Li; Juwei Wang; Zhimin Wu; Na Zhao; Yue Jiang (Molecular Neurobiology, 2025)

IQGAP1 participates in bone marrow-derived macrophage recruitment and involves in liver inflammation/fibrosis - Na Chang; Yuehan Ma; Jing Liu; Weiyang Li; Jing Zhao; Yuran Liu; Fuquan Liu; Chengbin Dong; Chang Liu; Changbo Qi; Lin Yang; Liying Li (Journal of Molecular Medicine, 2025)

A fluorescent fiber pH sensor for sensitive, wide-range detection using orange-emitting silicon quantum dots - Dan Li; Xiaolong Li; Zijia Huang; Tengteng Liu; Mao Li; Xiaoming Chen; Na Li; Yong Zhao (Analytica Chimica Acta, 2025)

Ni nanoparticles inlaid in amorphous silicon nitride-derived nickel phyllosilicate: A highly stable and active catalyst for ammonia decomposition - Han Yang; Jing Li; Qiang Chang; Qun-chao Zhao; Meng-na Zhang; Huan-jiang Wang; Cheng-hua Zhang; Fei Wang; Xiao-dong Wen (Fuel, 2025)

Zinc-releasing adhesive oral patch for prevention of radiation-induced oral ulcerative mucositis - Xiang Li; Kai-Yan Wang; Wen Qin; Wei-Wei Yu; Xin-Yi Hao; Wen Niu; Xu-Fang Liu; Qing Liu; Jian-Hua Wei; Yao Zhao; Franklin R. Tay; Ling-Yun Xia; et al. (Chemical Engineering Journal, 2025)

Acetyl alkannin, a Shikonin monomer, inhibits the ATM/DDR pathway by targeting ATM and sensitizes cisplatin in solid tumors - Xinwen Xu; Jianyi Gu; Peiwen Yang; Lifang Huang; Na Zhao; Jingjing Tang; Zifeng Liang; Qiang Li; Shunqian Wen; Jianwei Jiang; Qing Zhang (Chemico-Biological Interactions, 2025)

The growth and nutrient removal properties of a newly isolated Desmodesmus sp. XNY-2104 under mixotrophic and heterotrophic conditions using volatile fatty acids (VFAs) - Jie Li; Na Liu; Wenbao Yan; Qi Zhao; Xinglong Zhou; Cong Jia; Chongqing Xu; Xiaozhe Song; Mingming Song (Biomass and Bioenergy, 2025)

Breaking genetic linkage barriers to improve brown planthopper resistance and grain yield in japonica rice - Wenhui Wang; Jun He; Yunlong Wang; Na Li; Quanguang Sun; Menglong Zhang; Qi Li; Haosen Xu; Kun Shao; Shihao Zhang; Shijia Liu; Liangming Chen; et al. (Theoretical and Applied Genetics, 2025)

Fermented Chinese herbal medicines combined with probiotics promote growth of fattening lambs under heat stress by modulating rumen mucosal barrier functions - Shoupei Zhao; Xinsheng Sun; Na Zhao; Hongwei Zhang; Gaofu Wang; Lu Zhang; Yuqing Liu; Haitong Yang; Jianjie Li; Jia Zhou; Yuhong Gao (Animal Feed Science and Technology, 2025)

Cytokine profiling in COVID-19 patients by using ion mobility-mass spectrometry-based parallel reaction monitoring - Ling Yan; Chenrui Yuan; Runhou Zhou; Li Zhong; Kelvin Kai-Wang To; Na Liu; Xin Diao; Guangshan Xie; Hongzhi Zhao; Haijiang Wu; Lin Zhu; Zhiwei Chen; et al. (Analytica Chimica Acta, 2025)

A novel Zn2+ probe for fluorescent monitoring of drug and E6/E7 protein interaction in living cells - Zhenzhen Xie; Lan Yu; Zuoping Li; Na Zhao; Shiwan You; Zhihao Zhao; Jindi Dou; Xiling Deng; Shiguo Sun (Analytica Chimica Acta, 2025)

Metabolome and Genome Analysis of a Novel Endophytic Fungus Aureobasidium pullulans KB3: Discovery of Polyketones and Polyketone Biosynthesis Pathway - Shuai Wang; Jia-Nuo He; Ying-Jie Wang; Wen-Ya Zhao; Qing-Xia Yang; Ya-Na Wang; Yang Zhang; Li-Ping Zhang; Hong-Wei Liu (Biochemical Genetics, 2025)

Quantitative assessment of coastal geomorphological and ecological damage risks: a case study of Sheyang coast - Dong Liang; Na Gao; Mingli Zhao; Mianrun Chen; Dongling Li; Haobing Cao; Zhaoyuan Zhang; Huamei Huang; Huaguo Zhang (Frontiers in Marine Science, 2025)
As critical zones of land–sea interaction, coastal areas serve as core regions for dense populations, economic development, and sustainable social progress. However, coastal erosion poses a significant challenge for China. Current risk management practices often rely on subjective judgment and lack standardized, quantifiable frameworks that integrate both subjective and objective perspectives. This study aims to develop a comprehensive classification framework for coastal degradation risk. By integrating the Analytic Hierarchy Process (AHP) and Criteria Importance Through Intercriteria Correlation (CRITIC) method using game theory, this framework effectively combines expert insights with empirical evidence. Six key indicators were collected for Sheyang coast over the past two decades, including shoreline change rate, nearshore mean wave height, nearshore mean current velocity, salt marsh vegetation area, mudflat area, and coastal slope. Based on the combined weights, coastal damage risk values were calculated. By leveraging the cloud model, critical thresholds were systematically identified to differentiate five risk levels—ranging from accretion to severe erosion—through a comprehensive assessment of shoreline siltation, shoreline stability, shoreline erosion accompanied by salt marsh vegetation disappearance, and steep slope formation with near-complete mudflat loss. This approach integrates multi-dimensional coastal parameters to establish a scientific framework for risk classification, enabling precise distinction between gradual sediment accumulation and catastrophic erosive degradation. The study reveals that the hydrodynamic conditions of Sheyang coast has gradually shifted from tide-dominated to wave-dominated, indicating a significant intensification of wave action in the region. The geomorphology evolved from wide tidal flats to steep erosional features, with a marked cumulative effect of coastal degradation, reflected in the escalation of risk level from level 2 to level 5. The proposed framework exhibits notable enhancements in both accuracy and adaptability, offering robust scientific support for targeted coastal zone management strategies. It not only elevates the precision of risk identification across dynamic coastal environments but also advances the methodological frontiers of coastal risk assessment.

Adaptive modeling method integrating slime mould algorithm and cascade ensemble: Nondestructive detection of silage quality under VIS-NIRS - Kai Zhao; Haiqing Tian; Jue Zhang; Li’na Guo; Yang Yu; Haijun Li (Computers and Electronics in Agriculture, 2025)

Taurine related pathways effect the potential domestication of wild Larimichthys crocea adapt to stress environment - Xubing Ba; Zhenjun Zhuang; Zebin Zhou; Jiayu Zhou; Qianwen Min; Biao Yuan; Xin Yi; Ruojing Li; Zhaoqiu Qu; Na Zhao; Bo Zhang (Aquaculture, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Intergenerational inequity from hydrological drought in a warming world - Rutong Liu; Kebing Chen; Jiabo Yin; Biqiong Wu; Yan Zhao; Zhiming Liang; Na Li; Fengxian Gao; Jing Tian; Yujie Zeng; Jiali Guo (Journal of Environmental Management, 2025)

Simultaneous detection of amino acids and short-chain fatty acids in tea using rapid pre-column derivatization coupled with GC–MS: Exploring their spatial distribution in tea trees and the impact of processing techniques on their content - Junren Xu; Jing Lu; Shanliang Fu; Na Li; Yiqiao Zhao; Kunbo Wang; Zhonghua Liu; Taolin Chen; Jianan Huang; Mingzhi Zhu (Food Chemistry, 2025)

The transcription factor CeWRI3 functions in TAG accumulation through activating CeOLE2 in Cyperus esculentus - Zhi Zou; Xiaowen Fu; Na Li; Panyan Zheng; Ruiling Wang; Hongyan Liu; Jiaquan Huang; Yongguo Zhao (Plant Cell Reports, 2025)

PM2.5 from biofuel smoke induces inflammatory response through the TRPC6/Ca2+/NLRP3 signaling pathway - Yan Chen; Na Zhan; Jinhuang Xu; Yupeng Huang; Yuying Su; Zhongqin Liu; Haisheng Feng; Wenxin Ji; Jiahao Liang; Shenting Zhao; Jianhua Li (Environmental Geochemistry and Health, 2025)

SSA-TCN: satellite clock offset prediction during outages of RTS stream - Lin Zhao; Zhibo Na; Liang Li; Peng Cui (GPS Solutions, 2025)

Exploring food-derived bioactive peptides: Efficacy, mechanisms, and clinical implications in ferroptosis regulation - Chenzhe Gao; Lin Zhang; Jiahui Ma; Haiyan Zhang; Yue Pang; Chenyu Xue; Dehai Li; Xiaoyu Zhao; Munkh-Amgalan Gantumur; Mizhou Hui; Weichen Hong; Yihong Bao; et al. (Trends in Food Science & Technology, 2025)

Causes and influencing mechanisms of differences in phosphorus occurrence forms in sediments of different types of urban lakes - Yinghai Zhu; Zeming Shi; Qian Li; Chengjie Zou; Na Zhang; Xinyu Wang; Kai Zhao (Science of The Total Environment, 2025)

Short-term PS-NP exposure in early adulthood induces neuronal damage in middle-aged mice via microglia-mediated neuroinflammation - Shan Shan; Dong Cheng; Hui Li; Wenhuan Yao; Ruirui Kou; Jing Ji; Na Liu; Tao Zeng; Xiulan Zhao (Journal of Hazardous Materials, 2025)

Rigid polyelectrolyte multilayer membrane with ultrahigh permeance and excellent dye/salt separation performance - Na Zhang; Fanglu Fu; Wen Bo; Hussein Baqiah; Li Zhao; Wenbo Lu; Yadi Cai; Jiahui Tian; Tingting Yan; Saisai Li; Shuyun Zheng; Qiang Li (Journal of Environmental Chemical Engineering, 2025)

Microbial agents assisted aerobic co-composting of sheep manure and furfural residue: Maturation enhancement and microbial dynamic - Mao Li; Lingwei Jiang; Fei Li; Xuejun Zhang; huanjun Zhao; Na Duan (Journal of Environmental Chemical Engineering, 2025)

Rapid absolute quantification of glucose and fructose isomers in honey using a boronic acid-based reactive matrix by MALDI-TOF/TOF tandem mass spectrometry - Zhang-Na Qin; Jia-Min Chen; Jia-Wei Li; Zhen-Peng Zhen; Qi-Zhao Chen; Zhi-Qiang Zhang; Gui-Hua Wang; Yu-Feng Gao (Food Chemistry, 2025)

Development of corn straw lignin-based cling films for enhanced preservation of strawberries - Tao Yu; Tong Wang; Renguo Zhang; Chenglin Su; Shuang Cao; Yini Zhao; Hejing Wang; Jiaxing Li; Na Niu; Ligang Chen (Food Packaging and Shelf Life, 2025)

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Long Non-Coding RNAs: Crucial Regulators in Alzheimer’s Disease Pathogenesis and Prospects for Precision Medicine - Chenbo Yang; Yiwei Li; Chao Chen; Zexin Sun; Enjie Liu; Na Wei; Xiaonan Liu; Jiao Shu; Na Zhao; Miaomiao Sun (Molecular Neurobiology, 2025)

Co-variation of Host Gene Expression and Gut Microbiome in Intestine-Specific Spp1 Conditional Knockout Mice - Na Li; Guangqi Gao; Tao Zhang; Chunyan Zhao; Yue Zhao; Yong Zhang; Zhihong Sun (Current Microbiology, 2025)

The 3PM transformation potential of minimal residual disease in solid tumor management: a bibliometric analysis and review - Yining Chen; Xin Li; Suya Zhao; Yuchong Zhang; Haixu Wang; Fangjian Na; Qi Guan; Zhi Li; Heming Li; Mingfang Zhao (EPMA Journal, 2025)

MiR-134-5p/BDNF/TrkB/CREB signaling pathway involved in the depression-like behaviors in mice following exposure to benzo[a]pyrene - Tingyi Zhao; Huan Li; Yunge Jia; Na Xia; Xin Li; Hongmei Zhang (Metabolic Brain Disease, 2025)

Urban heat health risk inequality and its drivers based on local climate zones: A case study of Qingdao, China - Fei Guo; Guining Fan; Jun Zhao; Hongchi Zhang; Jing Dong; Hui Ma; Na Li (Building and Environment, 2025)

Ginsenoside CK modulates glucose metabolism via PPARγ to ameliorate SCOP-induced cognitive dysfunction - Na Li; Xingyu Fang; Hui Li; Jian Liu; Nan Chen; Xiaohui Zhao; Qing Yang; Xijun Chen (Metabolic Brain Disease, 2025)

Harnessing corn straw biochar: A breakthrough in eco-friendly Cu(II) wastewater treatment - Na Li; Fuchen Zhu; Zhaowei Wang; Jinghui Wu; Yidi Gao; Keqing Li; Chunliang Zhao; Xianze Wang (Waste Management, 2025)

Facile preparation of N/P co-doped mesoporous biochar for efficient removal of methylene blue from aqueous solutions: A 2D-FTIR-COS, adsorption mechanism analysis, and fixed-bed column study - Shisuo Fan; Manquan Zhao; Jiajia Luo; Weicheng Li; Xinru Fan; Na Zhou; Huacheng Xu; Yuanzhi Shi (Journal of Water Process Engineering, 2025)

The impact of Span80 single molecule and micelle forms on the structure and performance of polyamide nanofiltration membranes - Yue Miao; Xiaowen Huo; Yingying Zhao; Xiuling Liu; Haitao Wang; Jun Li; Na Chang (Journal of Water Process Engineering, 2025)

Magnetic graphene-enhanced exonuclease III assisted amplification strategy driven carbon nanozyme for tri-mode detection of Escherichia coli O157:H7 - Yuwei Ren; Lulu Cao; Zongyang Li; Xin Zhang; Hui Li; Rui Jiao; Xiaoyu Yu; Zhao Liang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; et al. (Food Chemistry, 2025)

Development of targeted antimicrobial peptides for Escherichia coli: Combining phage display and rational design for food safety application - Mingyang Hu; Yuwen Li; Sina Cha; Lu Zhao; Can Liu; Mingrui Sui; Chenyu Xue; Na Dong (Food Chemistry, 2025)

Non-targeted and targeted detection of hydrophilic compounds in fu brick tea: A study on samples from major Chinese production regions and different processing stages - Na Li; Mengmeng Zhao; Jin Chao; Feiyan Yin; Yong Yuan; Yiqiao Zhao; Junren Xu; Zhonghua Liu; Jianan Huang; Kunbo Wang; Mingzhi Zhu (Food Chemistry, 2025)

Exploring the bioactive ingredients of three traditional Chinese medicine formulas against age-related hearing loss through network pharmacology and experimental validation - Wenying Shi; Qi Zhao; Hongwei Gao; Yaxin Yang; Zhiyong Tan; Na Li; Hongjie Wang; Yonghua Ji; You Zhou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Involvement of BK Channels and Ryanodine Receptors in Salicylate-induced Tinnitus - Wenying Shi; Qi Zhao; Hongwei Gao; Chao Yang; Zhiyong Tan; Na Li; Feng Jiang; Hongjie Wang; Yonghua Ji; You Zhou (Molecular Neurobiology, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Tracking the nitrogen transformation in saline wastewater by marine anammox bacteria-based Fe(II)-driven autotrophic denitratation and anammox - Na Zhao; Panqing Qi; Jin Li; Bowei Tan; Weichuan Kong; Hui Lu (Water Research, 2025)

γ-Radiation synthesis of bis-amidoxime-based three-dimensional hydrogel uranium adsorbent based on nano-rubber toughening - Bo Tian; Wenze Li; Jianwei Zhang; Jinfeng Li; Na Zhou; Wa Gao; Nan Zhang; Hongtao Zhao (Journal of Water Process Engineering, 2025)

Metabolic landscape of human alveolar type II epithelial cells undergoing epithelial-mesenchymal transition induced directly by silica exposure - Jin Sun; Na Zhao; Ruijia Zhang; Yizheng Li; Tiantian Yu; Qiying Nong; Li Lin; Xubin Yang; Tiangang Luan; Baowei Chen; Yongshun Huang (Journal of Environmental Sciences, 2025)

Chameleon-inspired molecular imprinted polymer with bicolored states for visual and stable detection of diethylstilbestrol in water and food samples - Dongmei Li; Jiayue Zhou; Zhuxin Chang; Hongwei Zhao; Nan Zhang; Huan Xia; Linyuan Wang; Jie Zhao; Guanggui Yu; Zhongze Fang; Na Sai (Food Chemistry, 2025)

Efficient adsorption behavior of Fe-based ternary magnetic LDHs for naphthalene acetic acid: Role of Fe element - Ning Liu; Ti-Bo Fang; Ling-Xi Zhao; Na Li; Xiang-Feng Chen; Ru-Song Zhao (Environmental Research, 2025)

Microwave-responsive nanoencapsulated fluorescence thermometers for quantitative assessment of microscale localized heat regulation in chemical production - Kai Liu; Na Wang; Zongliang Kou; Xiaxin Jiao; Suguang Yang; Minghui Lyu; Hong Li; Zhenyu Zhao; Xin Gao (Chemical Engineering Journal, 2025)

Synergistic effects of acid-plasma treatment on CO2 capture towards carbon materials - Zhiping Ye; Chuang Han; Meilan Pan; Liang Zhao; Na Liu; Anton Nikiforov; Karen Leus; Nathalie De Geyter; Rino Morent; Jun Chen; Junhua Li (Chemical Engineering Journal, 2025)

Structure characteristics of a novel pectic polysaccharide from Fructus Corni and its protective effect on alcoholic fatty liver - Hong-Xin Bai; Yu-Xuan Gao; Shuyao Wang; Guang-Yuan Ma; Wenjing Zhao; Xiao-Qiang Li; Yu-Fan Wang; Qiu-Na Nong; Yu-Bo Wang; Jin Tan; Qimei Duan; Wei Cao (Carbohydrate Polymers, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

2D Laplace-Fourier domain acoustic wave equation modeling with an optimal finite-difference method - Jing-Yu Wang; Na Fan; Xue-Fei Chen; Shou-Rui Zhong; Bo-Yu Li; Dan Li; Gang Zhao (Applied Geophysics, 2025)

Integrated omics analysis reveals the effect of feeding scarcity on the lipid metabolism and apoptosis in Nibea coibor - Zhaoqiu Qu; Biao Yuan; Ruojing Li; Xubing Ba; Zhenjun Zhuang; Xin Yi; Jiayu Zhou; Qianwen Min; Zhongdian Dong; Na Zhao; Bo Zhang (Aquaculture, 2025)

Genetic diversity and genetic structure in successive mass selected generations of tetraploid Pacific oysters (Crassostrea gigas), diploid Portuguese oysters (C. angulata) and their allotriploid oysters - Haitao Ma; Yanping Qin; Yinjie Zhang; Weitao Wan; Jingyue Huang; Na Mi; Zhen Zhao; Zhongyu Wang; Jiangwei Li; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2025)

Phenylmethylsiloxanes in the typically human-impacted Xiaoqing River of China: Their distribution and degradation in both waterbodies and mussels - Nannan Liu; Wenxuan Jin; Chunsheng Qiu; Lin Xu; Xu Chen; Na Li; Rusong Zhao; Yaqi Cai (Journal of Hazardous Materials, 2025)

Slow sand filters with variable filtration rates for rainwater purification: Microecological differences between biofilm and water phases - Na Li; Xing Li; Li Zhao; Ze-Dong Lu; Yong-Wang Liu; Nan Wang (Journal of Environmental Management, 2025)

The growth and nutrient removal properties of heterotrophic microalgae using volatile fatty acids under different nitrogen forms and its application in actual acid-producing wastewater - Cong Jia; Na Liu; Lei Chen; Wenbao Yan; Qi Zhao; Jie Li; Ze Yu; Mingming Song; Chongqing Xu; Xiaozhe Song (Journal of Environmental Chemical Engineering, 2025)

Using multi-modal spectroscopy technology and microscopic analysis to explore the regulation of ultra-high pressure heat-assisted treatment on the texture of ready-to-eat shrimp during storage - Na Li; Zhifeng Tan; Ruida Ma; Yafang Song; Rong Liu; Jiaxin Zhao; Ningbo Qin; Yahong Li; Xiaoyang Liu; Dayong Zhou; Deyang Li (Food Chemistry, 2025)

Corrigendum to ‘A study of macroinvertebrate community structure and diversity in response to land use type in the Yiluo River Basin’ [Environ. Res. 255 (2024) 119157] - Na Zhao; Zhijun Yao; Weijun Chen; Chenxi Sang; Zhiwei Li; Xiaoli Niu; Feilong Gao (Environmental Research, 2025)

Allicin amplifies disulfidptosis during GOx catalyzing glucose-starvation for cancer therapy via simultaneous antimicrobial and antitumor intervention - Taotao Huo; Bin Zhu; Xiaoyu Shan; Jiaqi Song; Ziyi Wang; Jianxu Zhou; Xianpeng Zhang; Yuquan Bai; Chengcheng Liu; Yiyang Zhao; Na Mei; Yazhong Bu; et al. (Chemical Engineering Journal, 2025)

Effective enhancement of ramie anaerobic continuous flow degumming by chitosan and its microbiological mechanism - Xuehui Xie; Yiting Qin; Haonan Mo; Zhuoyu Zhao; Yuling Li; Yanxue Ma; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; Qingyun Zhang; Xiaoguang Chen (Bioresource Technology, 2025)

Ability of typical greening tree species to purify NO2 under different environmental factors - Jiaxing Fang; Shaoning Li; Mengxue Wang; Na Zhao; Xiaotian Xu; Bin Li; Junjie Zhang; Chen Liu; Qin Zhang; Shaowei Lu (Atmospheric Pollution Research, 2025)

Drought timing and degradation status determine the grassland sensitivity to simulated drought events - Shaoning Li; Shaowei Lu; Xijin Wang; Ziting Chen; Bin Li; Na Zhao; Xiaotian Xu (Agriculture, Ecosystems & Environment, 2025)

Enhancing the water use efficiency model predictions for Platycladus orientalis and Quercus variabilis: Integrating the dynamics of carbon dioxide concentration and soil water availability - Na Zhao; Shaowei Lu; Shaoning Li; Bin Li; Xinxiao Yu; Xiaotian Xu (Science of The Total Environment, 2025)

Benzofurans and dibenzofurans from galls on twigs of the endangered Chinese endemic tree Parrotia subaequalis and their inhibitory properties against Staphylococcus aureus and ATP-citrate lyase - Peng-Jun Zhou; Xi-Ying Wu; Ze-Yu Zhao; Yi Zang; Zhong-Shuai Sun; Yue-Ling Li; Na Li; Juan Xiong; Yeun-Mun Choo; Ze-Xin Jin; Jia Li; Jin-Feng Hu (Phytochemistry, 2025)

ALFIN-like proteins link histone H3K4me3 to H2A ubiquitination and coordinate diverse chromatin modifications in Arabidopsis - Xiao-Min Su; Dan-Yang Yuan; Na Liu; Zhao-Chen Zhang; Minqi Yang; Lin Li; She Chen; Yue Zhou; Xin-Jian He (Molecular Plant, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

BCDPi: An interpretable multitask deep neural network model for predicting chemical bioconcentration in fish - Zhaoyang Chen; Na Li; Ling Li; Zihan Liu; Wenqiang Zhao; Yan Li; Xin Huang; Xiao Li (Environmental Research, 2025)

Benefits of tidal admittance functions for refining GNSS-observed solar and lunisolar tidal constituents - Hao Wang; Na Wei; Min Li; Shin-Chan Han; Yunfei Xiang; Qile Zhao (GPS Solutions, 2025)

Host development promotes the early microbiota succession of teleost surpassing dietary management - Na Zhao; Ruojing Li; Xufeng Zhu; Biao Yuan; Chunhua Zhu; Bo Zhang (Aquaculture, 2024)

Optimization of vitrification methods for equine oocytes - Ming Du; Xinyu Li; Bayinnamula; Na Wang; Yuanyi Liu; Lei Zhang; Yiping Zhao; Manglai Dugarjaviin (Tissue and Cell, 2024)

Polystyrene nanoplastics induce apoptosis, histopathological damage, and glutathione metabolism disorder in the intestine of juvenile East Asian river prawns (Macrobrachium nipponense) - Yiming Li; Yucong Ye; Xiaoyi Zhu; Siwen Li; Na Rihan; Zongli Yao; Zhen Sun; Pengcheng Gao; Yunlong Zhao; Qifang Lai (Science of The Total Environment, 2024)

Effect of probiotic fermentation on the extraction rate and bioactivity of plant-based polysaccharides: A review - Zichao Wang; Yi Zheng; Yibo Dai; Rongchao Yang; Renyong Zhao; Gangchun Sun; Wen-Wen Zhou; Shouai Feng; Yingjie Feng; Na Li; Jinchu Yang; Huiru Zhang; et al. (Innovative Food Science & Emerging Technologies, 2024)

Novel insight into calcium-catalyzed steam gasification behaviors of lignite - Bin Zhao; Lufeng Liu; Quansheng Liu; Na Li; Huacong Zhou; Yanpeng Ban (Fuel, 2024)

Hydrophilic molecularly imprinted thermal-responsive polymers based sorbent for ambient ionization mass spectrometric analysis of sulfonamide antibiotics from food samples - Yaxin Hao; Minli Yang; Na Li; Yanfang Zhao; Yunshan Wang; Xiangfeng Chen; Feng Zhang (Food Chemistry, 2024)

The influence of processing methods on polyphenol profiling of tea leaves from the same large-leaf cultivar (Camellia sinensis var. assamica cv. Yunkang-10): nontargeted/targeted polyphenomics and electronic sensory analysis - Na Li; Junren Xu; Yiqiao Zhao; Mengmeng Zhao; Zhonghua Liu; Kunbo Wang; Jianan Huang; Mingzhi Zhu (Food Chemistry, 2024)

Assessment of the impact of whey protein hydrolysate on myofibrillar proteins in surimi during repeated freeze–thaw cycles: Quality enhancement and antifreeze potential - Xinyan Peng; Yunying Li; Juan Yu; Yonglin Gao; Xinxin Zhao; Na Jia (Food Chemistry, 2024)

Modulation of the receptor for advanced glycation end products pathway by natural polyphenols: A therapeutic approach to neurodegenerative diseases - Yinghao Wei; Yanqing Zhang; Jie Sun; Wei Li; Xiaotong Zhao; Na Tian; Yuxin Cao; Junbo Xie (Food Bioscience, 2024)

An eco-friendly, high-yield and scalable method for processing concentrated natural rubber latex with superabsorbent polymer beads - Shenbo Huang; Zirong Luo; Jizhen Zhang; Na Kong; Jihua Li; Pengfei Zhao; Jiayu Wu; Shaozao Tan; Jinlong Tao (Chemical Engineering Journal, 2024)

Ru induced charge redistribution of MnO2 spheric nanozyme boosted hydrogen sulfide selective detection and cystathionine γ-lyase activity sensitive evaluation - Zhao Li; Xuan Zhang; Haorong Cheng; Zhongyuan Gu; Changchun He; Ju Wang; Xinxin Shi; Weidan Na; Tongxiang Li; Lin Tian (Chemical Engineering Journal, 2024)

Morphology and elemental composition of individual solid dust particles: From different sources to the atmosphere - Wenhua Wang; Mengyang Wang; Longyi Shao; Xiuyan Zhou; Zhe Zhao; Na Li; Hui Zhou; Weijun Li (Atmospheric Environment, 2024)

Two new furanone derivatives from the endophytic fungus Byssochlamys sp. and their cytotoxic activities - Jie Wang; Wen-Bin Gao; Fan-Wei Liu; Qi Liu; Bo Song; Jin Ye; Ying Chen; Cai-Lin Zhao; Wei Dong; Li-Na Guo; Bo Song (Natural Product Research, 2024)

Identification of a novel intronic variant of ATP6V0A2 in a Han-Chinese family with cutis laxa - Ying Zhang; Mei Sun; Na Li; Yiran Zhao; Fang Zhang; Jianbo Shu; Yang Liu; Chunquan Cai (Molecular Biology Reports, 2024)

Corrigendum to “An innovative strategy for synchronous treatment of combined heavy metal and organic pollutants through polysaccharide gel encapsulating S2−” [Sci. Total Environ. 742 (2020), 140601] - Na Qi; Hui Zhao; Yan Qin; Qiaozhi Wang; Guojie Wang; Ying Li (Science of The Total Environment, 2024)

Unveiling the impacts of microplastic pollution on soil health: A comprehensive review - Nan Chang; Li Chen; Na Wang; Qingliang Cui; Tianyi Qiu; Shuling Zhao; Haoran He; Yi Zeng; Wei Dai; Chengjiao Duan; Linchuan Fang (Science of The Total Environment, 2024)

Impacts of future climate change on rice yield based on crop model simulation—A meta-analysis - Na Li; Yating Zhao; Jinsheng Han; Qiliang Yang; Jiaping Liang; Xiaogang Liu; Yazhou Wang; Zhengzhong Huang (Science of The Total Environment, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Phase change thermal interface film with bicontinuous and textured filler network for efficient wearable heat dissipation - Jia-Qing Zhao; Xiang Wang; Xun-Rui Wang; Hong-Wei Zhao; Mei-Na Lu; Wayne-Qiang Xu; Hong-En Nian; Jin-Hong Li (Chemical Engineering Journal, 2024)

Methylobacterium flocculans sp. nov., a Floc-Forming Bacterium Isolated from Aquaculture Ponds - Na Gao; Ting Fang; Yangyang Liang; Jing Li; Xiuxia Zhao; Wenxuan Lu (Current Microbiology, 2024)

Development and application of turbulent heat flux model for lead-bismuth eutectic based on deep learning - Li-Xia Chen; Chao Yuan; Jun-Long Zhao; Hong-Na Zhang; Xiao-Bin Li; Feng-Chen Li (Annals of Nuclear Energy, 2024)

The comparative techno-economic and life cycle assessment for multi-product biorefinery based on microwave and conventional hydrothermal biomass pretreatment - Na Wang; Kai Liu; Zhengkun Hou; Zhenyu Zhao; Hong Li; Xin Gao (Journal of Cleaner Production, 2024)

Beetle-inspired AuNPs semi-embedded colloidal crystal chips for the highly sensitive and colored detection of chloramphenicol in foods - Jiayue Zhou; Dongmei Li; Jie Nan; Nan Zhang; Hongwei Zhao; Huan Xia; Zhuxin Chang; Na Sai (Food Chemistry, 2024)

Strong interaction heterointerface of NiFe oxyhydroxide/cerium oxide for efficient and stable water oxidation - Han Jiao; Chun Wang; Hao Tian; Zi-Yang Zhang; Yang Zhao; Ping Na; Yusuke Yamauchi; Zhong-Li Wang (Chemical Engineering Journal, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Selective production of dihydroxyacetone and glyceric acid from glycerol photo-oxidation - Jiu Wang; Bo Liu; Zheng Li; Yejun Xiao; Heng Zhao; Liquan Jing; Na Zhong; Bei Li; Md Golam Kibria; Jinguang Hu (Chemical Engineering Journal, 2024)

Label-free SELEX of aptamers for ultra-sensitive electrochemical aptasensor detection of amanitin in wild mushrooms - Renxiang Yang; Changsong Zhao; Sheng Ding; Jia Ruan; Dongqiu Li; Yijia Xiang; Jie Zhou; Huilan Su; Na Li (Analytica Chimica Acta, 2024)

The association between short-term ozone exposure and fasting blood glucose levels in non-diabetic adults was more obvious in rural residents: the evidence from a typical “urban–rural dual structure” province in southwestern China - Xue-Jiao Li; Ling Li; Li Zhao; Ding-Yan Hu; Na-Na Ma; Hua Xiao; Da-Wei Li; Jie Zhou; Yi-Ying Wang; Ji Zhang; Tao Liu; Yue-Xu Jiang; et al. (Air Quality, Atmosphere & Health, 2024)

IRF9 and STAT1 as biomarkers involved in T-cell immunity in atherosclerosis - Wei Xie; Xiang Gao; Liang Zhao; Shifei Song; Na Li; Junming Liu (Journal of Biosciences, 2024)

In vitro generation of trophoblast like stem cells from goat pluripotent stem cells - Qin Na; Siyu Zhang; Peng Shao; Yu Jia; Yanqiu Wang; Mengyi Wei; Yanglin Chen; Chen Chen; Lixia Zhao; Zixin Wang; Yongli Song; Baojiang Wu; et al. (Theriogenology, 2024)

Separation of ovomucin from duck egg white and its “acid-tight /alkali-loose” self-supporting gel properties under different pH - Yao Yao; Yucheng Zhong; Han Li; Tiantian Liu; Na Wu; Shuping Chen; Lilan Xu; Yan Zhao; Yonggang Tu (Food Hydrocolloids, 2024)

Neutrophil-secreted S100A8/A9 participates in fatty liver injury and fibrosis by promoting myofibroblast migration - Na Chang; Yuran Liu; Weiyang Li; Yuehan Ma; Xuan Zhou; Xinhao Zhao; Lin Yang; Liying Li (Journal of Molecular Medicine, 2024)

Responses of the Arctic sea ice drift to general warming and intraseasonal oscillation in the local atmosphere - Ming Li; Xi Liang; Na Liu; Fu Zhao; Zhongxiang Tian (Climate Dynamics, 2024)

A DEM upscaling method with integrating valley lines based on HASM - Mingwei Zhao; Xiaoxiao Ju; Na Zhao; Chun Wang; Yan Xu; Xiaoran Wu; Weitao Li (Frontiers of Earth Science, 2024)

Impacts of non-linear ITRF2020 on reference frame alignment - Guo Chen; Na Wei; Hao Wang; Tao Li; Min Li; Qile Zhao (Advances in Space Research, 2024)

Association between residential greenness and incident delirium: A prospective cohort study in the UK Biobank - Qida He; Mengtong Sun; Yu Wang; Guoxian Li; Hanqing Zhao; Ze Ma; Zhaolong Feng; Tongxing Li; Qiang Han; Na Sun; Linyan Li; Yueping Shen (Science of The Total Environment, 2024)

Genomic profiling of biosynthetic potentials of medicinal secondary metabolites for ‘Aliisedimentitalea scapharcae’ KCTC 42119T, isolated from ark shell - Jin-Cheng Rong; Lin-Lin Cui; Na Li; Mao-Li Yi; Bo-Tao Huang; Qi Zhao (Marine Genomics, 2024)

Seaweeds as a major source of dietary microplastics exposure in East Asia - Xiangyang Xiao; Shaochong Liu; Lianzhen Li; Ruijie Li; Xiaoyu Zhao; Na Yin; Xilin She; Willie Peijnenburg; Xiumin Cui; Yongming Luo (Food Chemistry, 2024)

A study of macroinvertebrate community structure and diversity in response to land use type in the Yiluo River Basin - Na Zhao; Zhijun Yao; Weijun Chen; Chenxi Sang; Zhiwei Li; Xiaoli Niu; Feilong Gao (Environmental Research, 2024)

An efficient microwave-assisted method using ethyl lactate/water cosolvent for lignocellulosic biomass fractionation - Na Wang; Kai Liu; Anran Xu; Hong Li; Zhenyu Zhao; Xiaolei Fan; Xin Gao (Chemical Engineering Journal, 2024)

Spatiotemporal ozone concentration variations and their influencing factors in Zhejiang, China, 2018–2022: A geographically and temporally weighted regression - Yi Li; Qing Hou; Bingye Xu; Wenlong Zhao; Jinmei Ding; Lingling Jin; Qiaoli Zou; Xudong Tian; Shengchen Xu; Xin Sun; Na Chao (Atmospheric Pollution Research, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Photochemistry of plateau lake-derived dissolved organic matter: Reactive species generation and effects on 17β-estradiol photodegradation - Huaying Liu; Yi-na Tu; Yajie Lei; Die Zhou; Qilin Zhao; Yingjie Li; Wenjiao Pan (Journal of Hazardous Materials, 2024)

Targeted and untargeted metabolomics reveals meat quality in grazing yak during different phenology periods on the Qinghai-Tibetan Plateau - Tongqing Guo; Qian Zhang; Xungang Wang; Xianli Xu; Yalin Wang; Lin Wei; Na Li; Hongjin Liu; Linyong Hu; Na Zhao; Shixiao Xu (Food Chemistry, 2024)

Preparation of co-doped biochar to improve electron transfer and modulate 1O2 generation: Unraveling the radical-unradical mechanism - Jingyang Zhang; Shuyi Yang; Kexin Zhou; Jiaqi Zhao; Junbo Wang; Na Li; Yuanfei Wang; Yun Li; Tao E (Chemical Engineering Journal, 2024)

Dietary lipid supplementation alleviated the impacts of polystyrene nanoplastic exposure in Litopenaeus vannamei - Yiming Li; Yucong Ye; Haojuan Yuan; Siwen Li; Na Rihan; Xingguo Liu; Yunlong Zhao; Xuan Che (Aquatic Toxicology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

An empirical modeling of the D region ionosphere based on F 107 - Na Li; Jinsong Chen; Zhimei Tang; Lei Zhao; Zonghua Ding; Feifei Wang (Advances in Space Research, 2024)

Neural network based on convolution and self-attention fusion mechanism for plant leaves disease recognition - Yun Zhao; Yang Li; Na Wu; Xing Xu (Crop Protection, 2024)

Glucose dependent resistance associated with intestinal microbiota facilitate teleost to survive bacterial infection - Na Zhao; Yuting Liu; Jiamin Guo; Yubang Shen; Bo Zhang; Jiale Li (Aquaculture, 2024)

Effect of Lactobacillus fermentation on the structural feature, physicochemical property, and bioactivity of plant and fungal polysaccharides: A review - Zichao Wang; Yi Zheng; Xueyan Zhou; Xueqin Wang; Xirui Liu; Qiong Wang; Renyong Zhao; Minjie Gao; Zhitao Li; Yingjie Feng; Yongming Xu; Na Li; et al. (Trends in Food Science & Technology, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Partially knocking out NtPDK1a/1b/1c/1d simultaneously in Nicotiana tabacum using CRISPR/CAS9 technology results in auxin-related developmental defects - Qian-Wei Ren; Tian-Yao Liu; Hu-Jiao Lan; Zhen-Chao Li; Min-Jun Huang; Ya-Ting Zhao; Yu Chen; Li-Na Liao; Xiao-Han Ma; Jian-Zhong Liu (Plant Science, 2024)

The linkage between wintertime sea ice drift and atmospheric circulation in an Arctic ice-ocean coupled simulation - Xi Liang; Haibo Bi; Chengyan Liu; Xichen Li; Dakui Wang; Fu Zhao; Zhongxiang Tian; Ming Li; Na Liu (Ocean Modelling, 2024)

Carbon nanotube incorporated quaternized lignin-based loose nanofiltration membrane toward dye/salt separation - Zhenyu He; Na Zhang; Li Zhao; Zhenghua Li; Wanling Cui; Yuangang Zhu; Yi Wang; Huining Deng; Chengrun Si; Wen Bo; Jie Zhou; Shicai Xu; et al. (Journal of Environmental Chemical Engineering, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

Lipidomics studies reveal dynamic changes in polar lipids of developing endosperm of oat and wheat varieties with differing oil contents - Na Li; Yi Huang; Yingdong Zhao; Zheng Yang; Qingli Jia; Baili Feng; David C. Taylor; Chang Du; Meng Zhang (Food Chemistry, 2024)

Simulated logistical transport effects on textural change of wax apple using different packaging types during storage time - Wanqi Wei; Na Zhang; Baoqing Li; Tong Zhao; Chiyun Cheng; Cunkun Chen; Hao Deng; Ruixiang Yan (Food Packaging and Shelf Life, 2024)

High-performance antibacterial tight ultrafiltration membrane constructed by co-deposition of dopamine and tobramycin for sustainable high-salinity textile wastewater management - Wenyuan Ye; Fan Yu; Zijian Yu; Na Kong; Xiaoyan Lin; Riri Liu; Jiale Du; Xuan Huang; Ailiang Gu; Sotto Arcadio; Wenyi Zhang; Xuewei Li; et al. (Desalination, 2024)

Short-time potentiostatic assisted borate to induce the generation of ultrathin NiFe LDH active phase for industrial-level water oxidation - Yu Ma; Jia-Jun Wang; Xiao-Han Liu; Na Xu; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Carbazole-Based branched Poly(Aryl Piperidinium) membranes for Ultra-Stable anion exchange membrane fuel cells - Jiayao Yang; Jialin Zhao; Na Li; Yijia Lei; Jingyi Wu; Jian Gao; Shiyao Sun; Kuirong Feng; Yan Wang; Zhe Wang (Chemical Engineering Journal, 2024)

Enhancing proton transport in polyvinylidenedifluoride membranes and reducing biofouling for improved hydrogen production in microbial electrolysis cells - Na Zhao; Shujuan Meng; Xiaohu Li; Hong Liu; Dawei Liang (Bioresource Technology, 2024)

Energy metabolism analysis of exogenous glutamate on promoting co-accumulation of astaxanthin yield and biomass in Phaffia rhodozyma D3 - Chunyu Cai; Na Xu; Jiale Feng; Jiahua Zhang; Qianxi Zhao; Huimin Liu; Bo Nan; Xia Li; Yuhua Wang (Bioresource Technology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Electroacupuncture Inhibits Neuroinflammation Induced by Astrocytic Necroptosis Through RIP1/MLKL/TLR4 Pathway in a Mouse Model of Spinal Cord Injury - Hongdi Zhao; Xiaoqin Zong; Long Li; Na Li; Chunlei Liu; Wanchao Zhang; Juan Li; Cheng Yang; Siqin Huang (Molecular Neurobiology, 2024)

Cell-Cycle-related Protein Centromere Protein F Deficiency Inhibits Cervical Cancer Cell Growth by Inducing Ferroptosis Via Nrf2 Inactivation - Xin hui Tang; Tian nan Zhao; Li Guo; Xin yue Liu; Wei na Zhang; Ping Zhang (Cell Biochemistry and Biophysics, 2024)
Cervical cancer (CC) is one of the severe cancers that pose a threat to women’s health and result in death. CENPF, the centromere protein F, plays a crucial role in mitosis by regulating numerous cellular processes, such as chromosome segregation during mitosis. According to bioinformatics research, CENPF serves as a master regulator that is upregulated and activated in cervical cancer. Nevertheless, the precise biological mechanism that CENPF operates in CC remains unclear. The aim of this study was to analyze the function of CENPF on cervical cancer and its mechanism. We conducted immunohistochemistry and western blot analysis to examine the expression levels of CENPF in both cervical cancer tissues and cells. To explore the hidden biological function of CENPF in cell lines derived from CC, we applied lentivirus transfection to reduce CENPF manifestation. CENPF’s main role is to regulate ferroptosis which was assessed by analyzing Reactive Oxygen Species (ROS), malonaldehyde (MDA), etc. The vitro findings were further validated through a subcutaneous tumorigenic nude mouse model. Our research finding indicates that there is an apparent upregulation of CENPF in not merely tumor tissues but also cell lines in the carcinomas of the cervix. In vitro and vivo experimental investigations have demonstrated that the suppression of CENPF can impede cellular multiplication, migration, and invasion while inducing ferroptosis. The ferroptosis induced by CENPF inhibition in cervical cancer cell lines is likely mediated through the Nrf2/HO-1 pathway. The data herein come up with the opinion that CENPF may have a crucial role in influencing anti-cervical cancer effects by inducing ferroptosis via the triggering of the Nrf2/HO-1 signaling pathway.

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

DPP8/9 inhibition attenuates the TGF-β1-induced excessive deposition of extracellular matrix (ECM) in human mesangial cells via Smad and Akt signaling pathways - Ke Li; Yuzhan Zhang; Weihao Zhao; Rongrong Wang; Yan Li; Linting Wei; Li Wang; Xianghui Chen; Zhao Chen; Pengfei Liu; Na Nie; Xuefei Tian; et al. (Toxicology Letters, 2024)

Green manure removal with reduced nitrogen improves saline-alkali soil organic carbon storage in a wheat-green manure cropping system - Fangdi Chang; Hongyuan Zhang; Na Zhao; Peiyi Zhao; Jiashen Song; Ru Yu; Zhengrong Kan; Xiquan Wang; Jing Wang; Hanjiang Liu; Dongxun Han; Xinya Wen; et al. (Science of The Total Environment, 2024)

Luminescence chronology of the Xiachuan Paleolithic site in Shanxi Province, northern China: A comparison between OSL and post-IR IRSL ages - Na Zhao; Jianping Wang; Liping Zhou; Sanling Li; Haiyun Ren; Shuisheng Du (Quaternary International, 2024)

Biomass based oxygenates modified Fe-Mn oxide with improved surface lattice oxygen mobility for the chemical looping-oxidative dehydrogenation of ethane to ethylene - Kang Li; Guang Li; Zhiwei Zhao; Xiaohong Ding; Na Li; Shuqi Ma; Yulong Zhang (Fuel, 2024)

Meta-analysis of impacts of microplastics on plant heavy metal(loid) accumulation - Li Chen; Nan Chang; Tianyi Qiu; Na Wang; Qingliang Cui; Shuling Zhao; Fengyu Huang; Hansong Chen; Yi Zeng; Faqin Dong; Linchuan Fang (Environmental Pollution, 2024)

Multiple stimulus responsive of a novel naphthalenediimide-based 2D alkaline-earth metal MOF material: Hydrochromism, amine-/acid-induced chromism and ionochromism as well as visual artificial film application - Rong Huo; Ting Zhang; Li Xian Sun; Li Na Zhao; Yong Heng Xing; Feng Ying Bai (Chemical Engineering Journal, 2024)

Immune-related gene methylation prognostic instrument for stratification and targeted treatment of ovarian cancer patients toward advanced 3PM approach - Wenshuang Jia; Na Li; Jingjing Wang; Xiaoxia Gong; Serge Yannick Ouedraogo; Yan Wang; Junkai Zhao; Godfrey Grech; Liang Chen; Xianquan Zhan (EPMA Journal, 2024)

Crosstalk between autophagy and inflammasomes in ricin-induced inflammatory injury - Shiji Zhang; Na Zhao; Suli Song; Yanchun Wang; Yan Wang; Chengbiao Sun; Mingxin Dong; Mengqi Huo; Na Xu; Wensen Liu; Guorui Li (Toxicology and Applied Pharmacology, 2024)

Exposure to polystyrene nanoplastics induces apoptosis, autophagy, histopathological damage, and intestinal microbiota dysbiosis of the Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Haojuan Yuan; Na Rihan; Mingming Han; Xingguo Liu; Tian Zhu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Environmentally relevant concentrations of 2,3,7,8-TCDD induced inhibition of multicellular alternative splicing and transcriptional dysregulation - Bilin Zhao; Jiewei Deng; Mei Ma; Na Li; Junlin Zhou; Xinyan Li; Tiangang Luan (Science of The Total Environment, 2024)

Classification of natural gas hydrate resources: Review, application and prospect - Na Wei; Jun Pei; Haitao Li; Shouwei Zhou; Jinzhou Zhao; Bjørn Kvamme; Richard Banks Coffin; Liehui Zhang; Yao Zhang; Jin Xue (Gas Science and Engineering, 2024)

Lignin/mesoporous hollow silica nanosphere thin film nanocomposite loose nanofiltration membrane for dye/salt separation - Qiang Li; Wenge Sun; Bin Shang; Na Zhang; Li Zhao; Huining Deng; Peng Du; Mei Qiao; Jinlong Lu; Zengyu Wang (Desalination, 2024)

Melting-salt crystallization assisted controllable synthesis of core-shell zeolite catalyst for effective coupling of microwave hotspot and catalytic active site - Kai Liu; Qiuyan Ding; Na Wang; Zongliang Kou; Anran Xu; Hong Li; Zhenyu Zhao; Yilai Jiao; Xin Gao (Chemical Engineering Journal, 2024)

Effect of mixture microstructure/compatibility on the properties of type-A gelatin-dextran edible films - Ling Wu; Bo Cui; Die Dong; Zhengzong Wu; Jianpeng Li; Lu Lu; Na Wang; Katsuyoshi Nishinari; Meng Zhao (Carbohydrate Polymers, 2024)

Dissolved Mn2+ promotes microbially-catalyzed protodolomite precipitation in brackish oxidized water - Zuozhen Han; Jie Li; Yanyang Zhao; Qingyuan Chen; Xiao Gao; Kaiming Hu; Na Guo; Xiangyu Wei; Ruirui Meng; Chenlin Zhu; Maurice E. Tucker; Chao Han (Chemical Geology, 2024)

Understanding the causes of rapidly declining prediction skill of the East Asian summer monsoon rainfall with lead time in BCC_CSM1.1m - Na Wang; Hong-Li Ren; Yi Deng; Siyu Zhao (Climate Dynamics, 2024)

Variations in microbial residue carbon and its contribution to soil organic carbon after vegetation restoration on farmland: The case of Guinan County - Na Li; Yalin Wang; Lin Wei; Xungang Wang; Qian Zhang; Tongqing Guo; Xianli Xu; Na Zhao; Shixiao Xu (Organic Geochemistry, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Prioritization of the ecotoxicological hazard of PAHs towards aquatic species spanning three trophic levels using 2D-QSTR, read-across and machine learning-driven modelling approaches - Feifan Li; Peng Wang; Tengjiao Fan; Na Zhang; Lijiao Zhao; Rugang Zhong; Guohui Sun (Journal of Hazardous Materials, 2024)

Biopolymer films incorporated with chlorogenic acid nanoparticles for active food packaging application - Kaixuan Ma; Fan Li; Taotao Zhe; Xinyu Sun; Xinyuan Zhang; Ping Wan; Huan Na; Junnan Zhao; Li Wang (Food Chemistry, 2024)

Common vetch intercropping with reduced irrigation ensures potato production by optimizing microbial interactions - Ting Che; Xinyue Zhang; Mingyue He; Fei Wang; Na Li; Xiayun Zang; Zhuoliang Xiao; Yuanzhou Xu; Feng Hu; Yongfeng Ren; Huijuan Zhang; Li Xu; et al. (Field Crops Research, 2024)

Effects of airborne pollen on allergic rhinitis and asthma across different age groups in Beijing, China - Sun Zhaobin; Zhao Yuxin; An Xingqin; Gao Na; Li Ziming; Zhang Shuwen; Liang Yinglin; Ruan Wenxi; Bu Yaqin; Xin Jingyi; Li Shihong (Science of The Total Environment, 2024)

Polystyrene nanoplastics exposure alters muscle amino acid composition and nutritional quality of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

The hysteresis damage of cold exposure on tissue and transcript levels in mice - Jing Zhang; Shiwan You; Lan Yu; Yuling Zhang; Zuoping Li; Na Zhao; Bo Zhang; Lihua Kang; Shiguo Sun (Journal of Thermal Biology, 2024)

The enhanced visible-light-driven porous O/P-C3N4 for persulfate photoactivation: Enhanced removal of refractory pollutants and lignin valorization - Liquan Jing; Yuanguo Xu; Meng Xie; Chongchong Wu; Xia Du; Heng Zhao; Na Zhong; Huaming Li; Ian D. Gates; Jinguang Hu (Chemical Engineering Journal, 2024)

Performance of green solvents in microwave-assisted pretreatment of lignocellulose - Na Wang; Anran Xu; Kai Liu; Zhenyu Zhao; Hong Li; Xin Gao (Chemical Engineering Journal, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Mixed sowing of Feed rape and Vicia villosa can substitute nitrogen fertilizer to improve soil multifunctionality in the Hetao irrigation District - Ru Yu; Hongyuan Zhang; Fangdi Chang; Jiashen Song; Jing Wang; Xiquan Wang; Zhengrong Kan; Na Zhao; Xiaohong Li; Jun Ma; Yuyi Li (CATENA, 2024)

Deciphering performance and microbial characterization of marine anammox bacteria-based consortia treating nitrogen-laden hypersaline wastewater: Inhibiting threshold of salinity - Zhaopeng Qu; Chen Tan; Xiaocui Wang; Na Zhao; Jin Li (Bioresource Technology, 2024)

Response of marine anammox bacteria to long-term hydroxylamine stress: Nitrogen removal performance and microbial community dynamics - Na Zhao; Yanling Qiu; Zhaopeng Qu; Jin Li (Bioresource Technology, 2024)

Nitrogen-mediated distinct rhizosphere soil microbes contribute to Sorghum bicolor (L.) Moench and Solanum nigrum L. for phytoremediation of cadmium-polluted soil - Jiawen Wu; Na Zhao; Xiaoxiao Li; Pan Zhang; Ting Li; Yuan Lu (Plant and Soil, 2024)

Gemfibrozil Alleviates Cognitive Impairment by Inhibiting Ferroptosis of Astrocytes via Restoring the Iron Metabolism and Promoting Antioxidant Capacity in Type 2 Diabetes - Nan Wang; Yujing Zhao; Meiyan Wu; Na Li; Chaoying Yan; Hongyan Guo; Qiao Li; Qing Li; Qiang Wang (Molecular Neurobiology, 2024)

Soil rare microorganisms mediated the plant cadmium uptake: The central role of protists - Xingguo He; Xian Xiao; Weiwei Wei; Liangzhong Li; Yuan Zhao; Na Zhang; Mingyu Wang (Science of The Total Environment, 2024)

Polystyrene nanoplastics induce lipid metabolism disorder and alter fatty acid composition in the hepatopancreas of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Uptake and distribution of the inorganic components NH4+ and NO3− in PM2.5 by two Chinese conifers - Jiaxing Fang; Shaoning Li; Na Zhao; Xiaotian Xu; Yongbin Zhou; Shaowei Lu (Science of The Total Environment, 2024)

Daily monitoring of Effective Green Area Index and Vegetation Chlorophyll Content from continuous acquisitions of a multi-band spectrometer over winter wheat - Wenjuan Li; Marie Weiss; Sylvain Jay; Shanshan Wei; Na Zhao; Alexis Comar; Raul Lopez-Lozano; Benoit De Solan; Qiangyi Yu; Wenbin Wu; Frédéric Baret (Remote Sensing of Environment, 2024)

Effect of ferric ions on Cronobacter sakazakii growth, biofilm formation, and swarming motility - Yang Wang; Na Ling; Yaping Wang; Dexin Ou; Zhao Liang; Guoqing Li; Hongyuan Zhao; Yingwang Ye (International Journal of Food Microbiology, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

The spatiotemporal variation of land surface heat fluxes in Tibetan Plateau during 2001–2022 - Na Li; Ping Zhao; Changyan Zhou (Atmospheric Research, 2024)

Characterization and fine mapping of a maize lesion mimic mutant (Les8) with enhanced resistance to Curvularia leaf spot and southern leaf blight - Jiankun Li; Tianyuan Fan; Ying Zhang; Ye Xing; Mengyao Chen; Ying Wang; Jie Gao; Na Zhang; Jinjun Tian; Chenyang Zhao; Sihan Zhen; Junjie Fu; et al. (Theoretical and Applied Genetics, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Improved estimation of ocean tide loading displacements using multi-GNSS kinematic and static precise point positioning - Hao Wang; Min Li; Na Wei; Shin-Chan Han; Qile Zhao (GPS Solutions, 2024)

Coagulation performance and floc characteristics of Fe–Ti–V ternary inorganic coagulant for organic wastewater treatment - Yuanyuan Geng; Yudong Nie; Hongfei Du; Tengfei Ma; Li Li; can Zhao; Na Xue; Qian Shen (Journal of Water Process Engineering, 2023)

A stable and efficient quasi-solid-state photo/betavoltaic-powered electrochemical cell based on 3-dimensional CdS/ZnO heterostructure - Zan Ding; Renrong Zheng; Wendi Zhao; Tongxin Jiang; Xue Li; Haisheng San; Xin Li; Lifeng Zhang; Na Wang (Chemical Engineering Journal, 2023)

Revolutionizing material design for protonic ceramic fuel cells: Bridging the limitations of conventional experimental screening and machine learning methods - Idris Temitope Bello; Daqin Guan; Na Yu; Zheng Li; Yufei Song; Xi Chen; Siyuan Zhao; Qijiao He; Zongping Shao; Meng Ni (Chemical Engineering Journal, 2023)

Estimation of GPS-observed ocean tide loading displacements with an improved harmonic analysis in the northwest European shelf - Hao Wang; Na Wei; Min Li; Shin-Chan Han; Rongxin Fang; Qile Zhao (Journal of Geodesy, 2023)

Comparative assessment of food safety regulations and standards for arsenic, cadmium, lead, mercury and iodine in macroalgae used as food and feed in China and Europe - Yingying Guo; Anne-Katrine Lundebye; Na Li; Åshild Ergon; Shaojun Pang; Yanhua Jiang; Wenjia Zhu; Yanfang Zhao; Xiaodong Li; Lin Yao; Lianzhu Wang; Inger Aakre (Trends in Food Science & Technology, 2023)

Contribution of the bacterial community of poorly fermented oat silage to biogas emissions on the Qinghai Tibetan Plateau - Chaosheng Liao; Binbin Na; Xiaolong Tang; Man Zhao; Changbing Zhang; Shiyong Chen; Minghong You; Binqiang Bai; Lizhuang Hao; Dorjeeh Tondrob; Guangpeng Qu; Shuqing Yang; et al. (Science of The Total Environment, 2023)

How much carbon dioxide has the Chinese PV manufacturing industry emitted? - Na Zhang; Yutian Jiang; Xiaojun Zhao; Jiawei Deng; Qianyu Mi; Jie Li (Journal of Cleaner Production, 2023)

Temporal patterns of algae in different urban lakes and their correlations with environmental variables in Xi'an, China - Shengnan Chen; Hanyan Liu; Haihan Zhang; Kai Li; Na Wang; Weimin Sun; Xiang Liu; Limin Niu; Ben Ma; Fan Yang; Haiyun Li; Daijuan Zhao; et al. (Journal of Environmental Sciences, 2023)

Accumulation of microbial necromass carbon and its contribution to soil organic carbon in artificial grasslands of various vegetation types - Na Li; Na Zhao; Shixiao Xu; Yalin Wang; Lin Wei; Qian Zhang; Tongqing Guo; Xungang Wang (European Journal of Soil Biology, 2023)

Selective extraction of uranium from seawater on amidoximated MXene/metal-organic framework architecture under an electric field - Nan Li; Li Yang; Ruidian Su; Na Shi; Jiakun Wu; Jia Zhao; Liping Wen; Zhining Wang (Desalination, 2023)

Carbon nano-onions acting as artificial pili enhance chloramphenicol degradation in an anaerobic membrane bioreactor - Ming-Chao Zhu; Yong-Ze Lu; Shou-Wen Chen; Zhao-Xia Hu; Jing-Wei Wang; Na Li; Raymond Jian-Xiong Zeng (Chemical Engineering Journal, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Transcriptomic analysis reveals novel desiccation tolerance mechanism of Cronobacter based on type VI secretion system inhibition - Yang Wang; Na Ling; Rui Jiao; Xiyan Zhang; Yuwei Ren; Hui Li; Wenhua Zhao; Qingping Wu; Yingwang Ye (Food Research International, 2023)

Effect of biochar-derived dissolved organic matter on tetracycline sorption by KMnO4-modified biochar - Kaiyue Yin; Juyuan Wang; Xiaofei Tian; Na Yu; Xuexue Zhang; Yingying Zhao; Yuehua Liu; Shunchang Sui; Cuiping Wang; Fei Lian; Sheng Zhai; Xiaoyun Li; et al. (Chemical Engineering Journal, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

CNIH4 governs cervical cancer progression through reducing ferroptosis - Jun-Yuan Yang; Dong Ke; Yanli Li; Jie Shi; Shi-Meng Wan; An-Jin Wang; Meng-Na Zhao; Han Gao (Chemico-Biological Interactions, 2023)

The coupling effects between acid-catalyzed hydrothermal pretreatment and acidic/alkaline deep eutectic solvent extraction for wheat straw fractionation - Na Pan; Baiheng Jiang; Jinguang Hu; Mei Huang; Jinsong He; Qin Jiang; Li Zhao; Fei Shen; Dong Tian (Bioresource Technology, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Oral administration of the herbal oligonucleotide XKC-sRNA-h3 prevents angiotensin II-induced hypertension in mice - Kegong Tang; Xiaona Wang; Yu Zhao; Xiaobei Li; Zhenyu Jiang; Song Mei; Mingrui Chen; Yiming Ma; Xinyi Du; Xiangyu Qiao; Na Sun; Jiaqi Liu; et al. (Science China Life Sciences, 2023)

Effect of environmental factors on expression of staphylococcal enterotoxin genes - Hong-na Li; Zhao-di Kang; Tao Wang; Tao Li; Yan-ge Yang; Wei-e Zhou; Fei Yuan (Environmental Science and Pollution Research, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Polystyrene nanoplastics decrease nutrient accumulation, disturb sex hormones, and inhibit reproductive development in juvenile Macrobrachium nipponense - Yiming Li; Yucong Ye; Na Rihan; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

Environmental hazard reduction and anti-aging enhancement of steel slag powder-asphalt mastic based on TiO2@UiO-67 composites - Yang Lv; Shaopeng Wu; Na Li; Huan Wang; Peide Cui; Haiqin Xu; Yuechao Zhao; Chao Yang; Xinxing Zhou; Serji Amirkhanian (Journal of Cleaner Production, 2023)

Association between phthalate exposure and obesity risk: A meta-analysis of observational studies - Qian Wu; Gang Li; Chen-Yang Zhao; Xiao-Lin Na; Yun-Bo Zhang (Environmental Toxicology and Pharmacology, 2023)

Phase behavior tuning enable high-safety and crack-free Ni-rich layered cathode for lithium-ion battery - Na Liu; Lai Chen; Haoyu Wang; Jiayu Zhao; Fei Gao; Jing Liu; Jinyang Dong; Yun Lu; Ning Li; Qi Shi; Yuefeng Su; Feng Wu (Chemical Engineering Journal, 2023)

Highly conductive and tough polyacrylamide/sodium alginate hydrogel with uniformly distributed polypyrrole nanospheres for wearable strain sensors - Yansong Zhang; Shuo Li; Zhongda Gao; Dejin Bi; Na Qu; Sanqing Huang; Xueqin Zhao; Renhong Li (Carbohydrate Polymers, 2023)

Insights into nitrogen removal and microbial response of marine anammox bacteria-based consortia treating saline wastewater: From high to moderate and low salinities - Chen Tan; Weidong Zhang; Yunna Wei; Na Zhao; Jin Li (Bioresource Technology, 2023)

Dppa3 Improves the Germline Competence of Pluripotent Stem Cells - Siying Liu; Shuang Zhao; Chuanyu Zhang; Chenglei Tian; Dan Wang; Huaxin Yu; Zongjin Li; Lin Liu; Na Liu (Stem Cell Reviews and Reports, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

Neuroprotective Effects of Oxymatrine via Triggering Autophagy and Inhibiting Apoptosis Following Spinal Cord Injury in Rats - Jian Li; Yang Cao; Lin-Na Li; Xin Chu; Yan-Song Wang; Jia-Jun Cai; Jin Zhao; Song Ma; Gang Li; Zhong-Kai Fan (Molecular Neurobiology, 2023)

Scutellarin Acts via MAPKs Pathway to Promote M2 Polarization of Microglial Cells - Hao-Lun Chen; Li Yang; Xiao-Li-Na Zhang; Qiu-Ye Jia; Zhao-Da Duan; Juan-juan Li; Li-yang Zheng; Teng-teng Liu; Zhi Qi; Yun Yuan; Chun-Yun Wu (Molecular Neurobiology, 2023)

Prediction of Effector Proteins from Trichoderma longibrachiatum Through Transcriptome Sequencing - Jialin Zhang; Lijun Wang; Aizhi Ren; Yinsheng Sheng; Xue Chang; Xiaolong Li; Mengjiao Guan; Na Shang; Peibao Zhao; Shulei Sun (Current Microbiology, 2023)

Effects of sporulation conditions on the growth, germination, and resistance of Clostridium perfringens spores - Dong Liang; Xiaoshuang Cui; Miaoyun Li; Yaodi Zhu; Lijun Zhao; Shijie Liu; Gaiming Zhao; Na Wang; Yangyang Ma; Lina Xu (International Journal of Food Microbiology, 2023)

Immune functions of the Dscam extracellular variable region in Chinese mitten crab - Xiao-Li Zhang; Guo-Qing Shen; Xiao-Na Zhang; Yue-Hong Zhao; Wei-Wei Li; Qun Wang (Fish & Shellfish Immunology, 2023)

Peroxydisulfate activation by CuFe2S3 nanocrystal doped C/N catalyst for phenanthrene degradation: Experimental, mechanism, and density functional theory calculation - Shaomeng Huang; Liping Wang; Qiongqiong He; Leilei Sun; Dan Li; Na Liu; Yaqin Zhao; Lei Yang (Chemical Engineering Journal, 2023)

Evaluation of GPS and BDS-3 broadcast earth rotation parameters: a contribution to the ephemeris rotation error - Wenwen Li; Guo Chen; Min Li; Na Wei; Yubin Wang; Qile Zhao (GPS Solutions, 2023)

Ecotoxicological QSAR study of fused/non-fused polycyclic aromatic hydrocarbons (FNFPAHs): Assessment and priority ranking of the acute toxicity to Pimephales promelas by QSAR and consensus modeling methods - Shuo Chen; Guohui Sun; Tengjiao Fan; Feifan Li; Yuancong Xu; Na Zhang; Lijiao Zhao; Rugang Zhong (Science of The Total Environment, 2023)

Simultaneous phosphorus removal and sludge reduction in continuous-flow reactor with granules under long sludge retention time - Na Yu; Yufeng Lv; Bin Li; Jianxiao Wang; Hao Mou; Yimin Zhao (Journal of Environmental Chemical Engineering, 2023)

Effects of dietary oat supplementation on carcass traits, muscle metabolites, amino acid profiles, and its association with meat quality of Small-tail Han sheep - Li-wei Wang; Shao-feng Su; Jie Zhao; Xiao-long He; Shao-yin Fu; Biao Wang; Yun-fei Wang; Da-qing Wang; Na-na Yun; Xin Chen; Damien P Belobrajdic; Terigele; et al. (Food Chemistry, 2023)

De-clustered nonbonding oxygen state inhibits oxygen dimerization for highly activated and stable anionic redox in sodium-based layered cathodes - Na Li; Enyue Zhao; Zhigang Zhang; Wen Yin; Bao-Tian Wang; Xiaoling Xiao (Chemical Engineering Journal, 2023)

Effects of bisphenols on lipid metabolism and neuro–cardiovascular toxicity in marine medaka larvae - Xueyou Li; Xiaoxu He; Xiaona Lin; Weihao Li; Jiahao Gao; Ning Zhang; Yusong Guo; Zhongduo Wang; Na Zhao; Bo Zhang; Zhongdian Dong (Aquatic Toxicology, 2023)

Upgrading the accumulation of ginsenoside Rd in Panax notoginseng by a novel glycosidase-producing endophytic fungus G11-7 - Lili Niu; Xiangyu Qin; Litao Wang; Na Guo; Hongyan Cao; Hanghang Li; Chunjian Zhao; Huimei Wang; Yujie Fu (Folia Microbiologica, 2023)

Cropland abandonment alleviates soil carbon emissions in the North China Plain - Lingjie Lei; Ying Li; Zhenxing Zhou; Na Li; Cancan Zhao; Qiang Li (Environmental Monitoring and Assessment, 2023)

Metformin alleviates the cognitive impairment induced by benzo[a]pyrene via glucolipid metabolism regulated by FTO/FoxO6 pathway in mice - Tingyi Zhao; Huide Miao; Zhanfei Song; Yangyang Li; Na Xia; Zhiyan Zhang; Hongmei Zhang (Environmental Science and Pollution Research, 2023)

Measurement and real-time monitoring of marine economic security climate in China - Xuemei Li; Shiwei Zhou; Yufeng Zhao; Na Li; Yuyu Sun (Ocean & Coastal Management, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Managing plant density and nitrogen fertilizer to reduce nitrogen input without yield reduction of late-sown cotton after wheat by improving light interception and sink nitrogen partitioning in a double cropping system - Zhao Zhang; Shoaib Ahmed; Muhammad Sohaib Chattha; Anda Liu; Jiahao Liu; Na Lv; Lirong Yang; Xuefeng Ma; Xian'en Li; Feiran Hao; Guozheng Yang (Field Crops Research, 2023)

Genome-wide association analysis of resistance to frogeye leaf spot China race 7 in soybean based on high-throughput sequencing - Chen Na; Huanran Miao; Haipeng Jiang; Jinglin Ma; Hongliang Liu; Suchen Lv; Jinghang Zhou; Yuming Yang; Yuhang Zhan; Weili Teng; Yonguang Li; Xue Zhao; et al. (Theoretical and Applied Genetics, 2023)

Selection of the appropriate reference genes by quantitative real-time PCR in leopard coral groupers Plectropomus leopardus - Han Zhang; Haoran Yang; Pengsuo Li; Na Zhao; Xiaojuan Chen; Yongcan Zhou; Zhenjie Cao; Yun Sun (Journal of Oceanology and Limnology, 2023)

Euphorfinoids A and B, a pair of ent -atisane diterpenoid epimers from the roots of Euphorbia fischeriana, and their bioactivities - Jiang-Chun Wei; Yu-Ning Gao; Hui-Hui Huang; Xiao-Yu Zhang; Xuan-Li Liu; Xiao-Xu Gao; Na Li; Yue Zhao; An-Hua Wang; Jing-Ming Jia (Natural Product Research, 2023)

Contributions of ectomycorrhizal fungi in a reclaimed poplar forest (Populus yunnanensis) in an abandoned metal mine tailings pond, southwest China - Yinrun Xiao; Conglong Liu; Na Hu; Bowen Wang; Kuanyu Zheng; Zhiwei Zhao; Tao Li (Journal of Hazardous Materials, 2023)

Lignin-based covalent organic polymers with improved crystallinity for non-targeted analysis of chemical hazards in food samples - Zhan-Chao Li; Wei Li; Rui Wang; Dong-Xia Wang; An-Na Tang; Xiao-Peng Wang; Xiao-Ping Gao; Gai-Ming Zhao; De-Ming Kong (Journal of Hazardous Materials, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Comparison of two commercial methods with a UHPLC–MS/MS method for the determination of multiple mycotoxins in cereals - Ying-yue Zhang; Mei-juan Zhao; Chun-yao Liu; Kai Ma; Tian-yu Liu; Fei Chen; Li-na Wu; De-jun Hu; Guang-ping Lv (Food Chemistry, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

Obstructive sleep apnea-increased DEC1 regulates systemic inflammation and oxidative stress that promotes development of pulmonary arterial hypertension - Xiaoming Li; Xiang Zhang; Xiaozhi Hou; Xin Bing; Fangyuan Zhu; Xinhao Wu; Na Guo; Hui Zhao; Fenglei Xu; Ming Xia (Apoptosis, 2023)

Corrigendum to “An advanced Ca/Zn hybrid battery enabled by the dendrite-free zinc anode and a reversible calcification/decalcification NASICON cathode” [Sci Bull 68 (2023) 56–64] - Shunshun Zhao; Chuanlin Li; Xixi Zhang; Na Li; Tongkai Wang; Xiaojuan Li; Chenggang Wang; Guangmeng Qu; Xijin Xu (Science Bulletin, 2023)

Quality assessment of variable collagen tissues of sea cucumber (Stichopus japonicus) body wall under different heat treatment durations by label-Free proteomics analysis - Yi-Zhen Huang; Yi-Sha Xie; Yan-Xin Li; Mei-Yu Zhao; Na Sun; Hang Qi; Xiu-Ping Dong (Food Research International, 2023)

Application of a novel and green temperature-responsive deep eutectic solvent system to simultaneously extract and separate different polar active phytochemicals from Schisandra chinensis (Turcz.) Baill - Xin-Yu Yan; Zi-Hui Cai; Peng-Quan Zhao; Jian-Dong Wang; Li-Na Fu; Qi Gu; Yu-Jie Fu (Food Research International, 2023)

Polarity-extended composition profiling via LC-MS-based metabolomics approaches: A key to functional investigation of Citrus aurantium L - Wen Miao; Xiaojing Liu; Na Li; Xiqing Bian; Yiran Zhao; Jing He; Tingting Zhou; Jian-Lin Wu (Food Chemistry, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

The combined effects of NaCl-pH and urea-pH on the phase separation of type-A gelatin and dextran - Qi Wang; Bo Cui; Li Guo; Zhao Li; Qingqing Chai; Na Wang; Die Dong; Katsuyoshi Nishinari; Meng Zhao (Food Hydrocolloids, 2023)

Enhanced H2O2 formation and norfloxacin removal by electro-Fenton process using a surface-reconstructed graphite felt cathode: New insight into synergistic mechanism of defective active sites - Hongkai Guo; Chengwen Zhao; Hu Xu; Honglin Hao; Ziyuan Yang; Na Li; Weijun Xu (Environmental Research, 2023)

Wet-spinning fluorescent alginate fibres achieved by doping PEI modified CPDs for multiple anti-counterfeiting - Li Song; Xiaolan Qiao; Jianxin Sun; Na Yi; Mengyue Wang; Zhihui Zhao; Ruyi Xie; Weichao Chen; Yanzhi Xia (Carbohydrate Polymers, 2023)

Analysis of PAT1 subfamily members in the GRAS family of upland cotton and functional characterization of GhSCL13-2A in Verticillium dahliae resistance - Chen Chen; Li-Li Lu; Shu-Ya Ma; Yan-Peng Zhao; Na Wu; Wen-Jie Li; Li Ma; Xian-Hui Kong; Zong-Ming Xie; Yu-Xia Hou (Plant Cell Reports, 2023)

Impacts of the long-term atmospheric trend on the seasonality of Antarctic sea ice - Fu Zhao; Xi Liang; Zhongxiang Tian; Chengyan Liu; Xichen Li; Yun Yang; Ming Li; Na Liu (Climate Dynamics, 2023)

Influence of cadmium and copper mixtures to rhizosphere bacterial communities - Qirui An; Yunyang Li; Na Zheng; Jincai Ma; Shengnan Hou; Siyu Sun; Sujing Wang; Pengyang Li; Xiaoqian Li; Chunmei Zhao (Soil Ecology Letters, 2023)

Metagenomics analysis reveals potential pathways and drivers of piglet gut phage-mediated transfer of ARGs - Yalu Ji; Hengyu Xi; Zhen Zhao; Qiujie Jiang; Chong Chen; Xinwu Wang; Fengyang Li; Na Li; Changjiang Sun; Xin Feng; Liancheng Lei; Wenyu Han; et al. (Science of The Total Environment, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Ecotoxicological QSAR modelling of the acute toxicity of fused and non-fused polycyclic aromatic hydrocarbons (FNFPAHs) against two aquatic organisms: Consensus modelling and comparison with ECOSAR - Feifan Li; Guohui Sun; Tengjiao Fan; Na Zhang; Lijiao Zhao; Rugang Zhong; Yongzhen Peng (Aquatic Toxicology, 2023)

IL-17A promotes endothelial cell senescence by up-regulating the expression of FTO through activating JNK signal pathway - Na Li; Runan Luo; Wenlong Zhang; Yu Wu; Chaojie Hu; Manli Liu; Diya Jiang; Ziran Jiang; Xinxin Zhao; Yiping Wang; Qing Li (Biogerontology, 2023)

A Review and Perspective of Environmental Disinfection Technology Based on Microwave Irradiation - Liming Liu; Na Wang; Azhar Ali Laghari; Hong Li; Can Wang; Zhenyu Zhao; Xin Gao; Qiang Zeng (Current Pollution Reports, 2023)

An advanced Ca/Zn hybrid battery enabled by the dendrite-free zinc anode and a reversible calcification/decalcification NASICON cathode - Shunshun Zhao; Chuanlin Li; Xixi Zhang; Na Li; Tongkai Wang; Xiaojuan Li; Chenggang Wang; Guangmeng Qu; Xijin Xu (Science Bulletin, 2023)

Performance and VOCs emission inhibition of environmentally friendly rubber modified asphalt with UiO-66 MOFs - Yang Lv; Shaopeng Wu; Na Li; Peide Cui; Huan Wang; Serji Amirkhanian; Zenggang Zhao (Journal of Cleaner Production, 2023)

Bioinspired green tea waste/graphene aerogel for solar-enhanced uranium extraction from seawater - Nan Li; Jiakun Wu; Ruidian Su; Na Zhang; Jia Zhao; Zhining Wang (Desalination, 2023)

Efficient H2 production in a novel separator electrode assembly (SEA) microbial electrolysis cell - Na Zhao; Dawei Liang; Hong Liu; Shujuan Meng; Xiaohu Li (Chemical Engineering Journal, 2023)

Oxygen-rich vacancy nickel–cobalt oxide cathode with low temperature adaptability for high-rate performance of alkaline zinc battery - Xiaojuan Li; Tongkai Wang; Chuanlin Li; Na Li; Shunshun Zhao; Xixi Zhang; Guangmeng Qu; Weijie Zhang; Xijin Xu (Chemical Engineering Journal, 2023)

Treadmill Exercise Improves PINK1/Parkin-Mediated Mitophagy Activity Against Alzheimer’s Disease Pathologies by Upregulated SIRT1-FOXO1/3 Axis in APP/PS1 Mice - Na Zhao; Xianliang Zhang; Baixia Li; Jing Wang; Chenfei Zhang; Bo Xu (Molecular Neurobiology, 2023)

Suppression of Wnt/β-Catenin Signaling Is Associated with Downregulation of Wnt1, PORCN, and Rspo2 in Alzheimer’s Disease - Jesse R. Macyczko; Na Wang; Jing Zhao; Yingxue Ren; Wenyan Lu; Tadafumi C. Ikezu; Na Zhao; Chia-Chen Liu; Guojun Bu; Yonghe Li (Molecular Neurobiology, 2023)

Visualizing Seizure Propagation in Freely-moving Mice via Miniature Two-photon Microscopy - Zhuoran Zhang; Shihe Jiang; Kaibin Shi; Yan Li; Wei-Na Jin; Qiang Liu; Ting Zhao; Heping Cheng; Fu-Dong Shi (Neuroscience Bulletin, 2022)

The cAMP‐PKA signalling pathway regulates hyphal growth, conidiation, trap morphogenesis, stress tolerance, and autophagy in Arthrobotrys oligospora - Mei‐Chen Zhu; Na Zhao; Yan‐Kun Liu; Xue‐Mei Li; Zheng‐Yi Zhen; Ya‐Qing Zheng; Ke‐Qin Zhang; Jin‐Kui Yang (Environmental Microbiology, 2022)
The cyclic adenosine monophosphate‐protein kinase A (cAMP‐PKA) signalling pathway is evolutionarily conserved in eukaryotes and plays a crucial role in defending against external environmental challenges, which can modulate the cellular response to external stimuli. Arthrobotrys oligospora is a typical nematode‐trapping fungus that specializes in adhesive networks to kill nematodes. To elucidate the biological roles of the cAMP‐PKA signalling pathway, we characterized the orthologous adenylate cyclase AoAcy, a regulatory subunit (AoPkaR), and two catalytic subunits (AoPkaC1 and AoPkaC2) of PKA in A. oligospora by gene disruption, transcriptome, and metabolome analyses. Deletion of Aoacy significantly reduced the levels of cAMP and arthrobotrisins. Results revealed that Aoacy , AopkaR , and AopkaC1 were involved in hyphal growth, trap morphogenesis, sporulation, stress resistance, and autophagy. In addition, Aoacy and AopkaC1 were involved in the regulation of mitochondrial morphology, thereby affecting energy metabolism, whereas AopkaC2 affected sporulation, nuclei, and autophagy. Multi‐omics results showed that the cAMP‐PKA signalling pathway regulated multiple metabolic and cellular processes. Collectively, these data highlight the indispensable role of cAMP‐PKA signalling pathway in the growth, development, and pathogenicity of A. oligospora, and provide insights into the regulatory mechanisms of signalling pathways in sporulation, trap formation, and lifestyle transition.

Effects of rainfall and rocky desertification on soil erosion in karst area of Southwest China - Li-dong Pan; Rui Li; Dong-cai Shu; Li-na Zhao; Mei Chen; Jun Jing (Journal of Mountain Science, 2022)

Rab11a promotes the malignant progression of ovarian cancer by inducing autophagy - Yazhuo Wang; Yanan Ren; Na Li; Jing Zhao; Sufen Zhao (Genes & Genomics, 2022)

The Location Reliability of the Resting-State fMRI FC of Emotional Regions Towards rTMS Therapy - Na Zhao; Juan Yue; Zi-Jian Feng; Yang Qiao; Qiu Ge; Li-Xia Yuan; Jue Wang; Yu-Tao Xiang; Yu-Feng Zang (Neuroinformatics, 2022)

CircPVT1 facilitates the progression of oral squamous cell carcinoma by regulating miR-143-3p/SLC7A11 axis through MAPK signaling pathway - Shiliang Wang; Wenlu Li; Long Yang; Jianqiao Yuan; Lin Wang; Na Li; Hongyu Zhao (Functional & Integrative Genomics, 2022)

BDS-3 and GPS/Galileo integrated PPP using broadcast ephemerides - Guo Chen; Na Wei; Min Li; Qile Zhao; Jiangnan Zhang (GPS Solutions, 2022)

Increased serum anti-CYP2E1 IgG autoantibody levels may be involved in the pathogenesis of occupational trichloroethylene hypersensitivity syndrome: a case–control study - Tamie Nakajima; Hailan Wang; Yuan Yuan; Yuki Ito; Hisao Naito; Yoshiyuki Kawamoto; Kozue Takeda; Kiyoshi Sakai; Na Zhao; Hongling Li; Xinxiang Qiu; Lihua Xia; et al. (Archives of Toxicology, 2022)
Occupational exposure to trichloroethylene (TCE) causes a systemic skin disorder with hepatitis known as TCE hypersensitivity syndrome (TCE-HS). Human Leukocyte Antigen (HLA)-B*13:01 is its susceptibility factor; however, the immunological pathogenesis of TCE-HS remains unknown. We herein examined the hypothesis that autoantibodies to CYP2E1 are primarily involved in TCE-HS. A case–control study of 80 TCE-HS patients, 186 TCE-tolerant controls (TCE-TC), and 71 TCE-nonexposed controls (TCE-nonEC) was conducted to measure their serum anti-CYP2E1 antibody (IgG) levels. The effects of TCE exposure indices, such as 8-h time-weighted-average (TWA) airborne concentrations, urinary metabolite concentrations, and TCE usage duration; sex; smoking and drinking habits; and alanine aminotransferase (ALT) levels on the antibody levels were also analyzed in the two control groups. There were significant differences in anti-CYP2E1 antibody levels among the three groups: TCE-TC > TCE-HS patients > TCE-nonEC. Antibody levels were not different between HLA-B*13:01 carriers and noncarriers in TCE-HS patients and TCE-TC. The serum CYP2E1 measurement suggested increased immunocomplex levels only in patients with TCE-HS. Multiple regression analysis for the two control groups showed that the antibody levels were significantly higher by the TCE exposure. Women had higher antibody levels than men; however, smoking, drinking, and ALT levels did not affect the anti-CYP2E1 antibody levels. Anti-CYP2E1 antibodies were elevated at concentrations lower than the TWA concentration of 2.5 ppm for TCE exposure. Since HLA-B*13:01 polymorphism was not involved in the autoantibody levels, the possible mechanism underlying the pathogenesis of TCE-HS is that TCE exposure induces anti-CYP2E1 autoantibody production, and HLA-B*13:01 is involved in the development of TCE-HS.

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

A superior allele of the wheat gene TaGL3.3-5B, selected in the breeding process, contributes to seed size and weight - Chaojie Wang; Lili Zhang; Yongdun Xie; Xiaofeng Guo; Yanfang Zhang; Yamin Zhang; Ahsan Irshad; Yuting Li; Huihui Qian; Doudou Jing; Guangyao Liu; Kaiming Wu; et al. (Theoretical and Applied Genetics, 2022)

CaMKIIα Signaling Is Required for the Neuroprotective Effects of Dl-3-n-Butylphthalide in Alzheimer’s Disease - Bing-qiu Li; Ling-zhi Xu; Fang-yu Li; Ying Li; Yu Zhao; Heng Zhang; Mei-na Quan; Jian-ping Jia (Molecular Neurobiology, 2022)

The Mechanism of Stem Cell Aging - Liangyu Mi; Junping Hu; Na Li; Jinfang Gao; Rongxiu Huo; Xinyue Peng; Na Zhang; Ying Liu; Hanxi Zhao; Ruiling Liu; Liyun Zhang; Ke Xu (Stem Cell Reviews and Reports, 2022)
Stem cells have self-renewal ability and multi-directional differentiation potential. They have tissue repair capabilities and are essential for maintaining the tissue homeostasis. The depletion of stem cells is closely related to the occurrence of body aging and aging-related diseases. Therefore, revealing the molecular mechanisms of stem cell aging will set new directions for the therapeutic application of stem cells, the study of aging mechanisms, and the prevention and treatment of aging-related diseases. This review comprehensively describes the molecular mechanisms related to stem cell aging and provides the basis for further investigations aimed at developing new anti-stem cell aging strategies and promoting the clinical application of stem cells.

Heterogeneity of the Tissue-specific Mucosal Microbiome of Normal Grass Carp (Ctenopharyngodon idella) - Na Zhao; Jiamin Guo; Bo Zhang; Kai Liu; Yuting Liu; Yubang Shen; Jiale Li (Marine Biotechnology, 2022)

HTRPCA: Hypergraph Regularized Tensor Robust Principal Component Analysis for Sample Clustering in Tumor Omics Data - Yu-Ying Zhao; Cui-Na Jiao; Mao-Li Wang; Jin-Xing Liu; Juan Wang; Chun-Hou Zheng (Interdisciplinary Sciences: Computational Life Sciences, 2022)

A systematic review on active sites and functions of PIM-1 protein - Youyi Zhao; Aziz ur Rehman Aziz; Hangyu Zhang; Zhengyao Zhang; Na Li; Bo Liu (Human Cell, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

VSIG4 Attenuates NLRP3 and Ameliorates Neuroinflammation via JAK2-STAT3-A20 Pathway after Intracerebral Hemorrhage in Mice - Na Ji; Lirong Wu; Hui Shi; Qianlu Li; Anyong Yu; Zhao Yang (Neurotoxicity Research, 2022)

Decreased incidence of acute hemorrhagic conjunctivitis associated with enhanced public health intervention during the COVID-19 epidemic in China, 2020 - Li Zhang; Xiangyu Guo; Hui Jiang; Na Zhao; Wei Cheng; Wangli Xu; Shelan Liu (Archives of Virology, 2022)

Assessment of BDS-3 terrestrial reference frame realized by broadcast ephemeris: comparison with GPS/Galileo - Guo Chen; Na Wei; Min Li; Qile Zhao; Yujiao Niu; Hongliang Cai; Yinan Meng (GPS Solutions, 2022)

Alkaloids with acetylcholinesterase inhibitory activity from Corydalis racemosa (Thunb.) Pers - Hui-Na Yao; Zhi-Tian Peng; Yun-Feng Zhang; Di-Fa Liu; Bing-Feng Huang; Peng-Fei Tu; Yun-Fang Zhao; Hui-Xia Huo; Jun Li (Natural Product Research, 2021)

Comparative Mucous miRomics in Cynoglossus semilaevis Related to Vibrio harveyi Caused Infection - Na Zhao; Lei Jia; Guangli Li; Xiaoxu He; Chunhua Zhu; Bo Zhang (Marine Biotechnology, 2021)

Occurrence and distribution characteristics of antibiotic resistance genes in sediments between urban and rural of the Liaohe River Basin, China - Guangshui Na; Keyu Zhang; Hui Gao; Ruijing Li; Shuaichen Jin; Fuqiang Zhao; Haibo Zhang; Shisheng Li (Environmental Science and Pollution Research, 2021)

Molecular Cloning and Characterization of FAD6 Gene from Chia (Salvia hispanica L.) - Yufei Xue; Lejing Li; Xuemei Liu; Huanhuan Jiang; Yanping Zhao; Songzhen Wei; Na Lin; Yourong Chai (Biochemical Genetics, 2021)

Influence of elevation on bioregionalisation: A case study of the Sino‐Himalayan flora - Yun Liu; Jian‐Fei Ye; Hai‐Hua Hu; Dan‐Xiao Peng; Li‐Na Zhao; Li‐Min Lu; Wajid Zaman; Zhi‐Duan Chen (Journal of Biogeography, 2021)
Aim Elevation is an important factor that influences bioregionalisation in mountainous areas, but its effects are not well known. Taking the Sino‐Himalayan flora as a case, we aimed to test the effect of elevation on bioregionalisation and provide a regionalisation scheme of the Sino‐Himalayan flora. Location The Sino‐Himalaya (East Himalaya, the Hengduan Mountains and the Yunnan Plateau in China). Taxon Angiosperms. Methods We compiled distribution data and elevation ranges of angiosperms in the Sino‐Himalaya and adjacent areas and reconstructed a species‐level phylogenetic tree of 19,313 angiosperm species. The area was divided into 398 grid cells, each 1 × 1°. Nine datasets of different elevation ranges were then used to delineate the flora of the Sino‐Himalaya and adjacent areas using the phylogenetic dissimilarity approach. Results A comparison of nine regionalisation schemes of the Sino‐Himalayan flora based on different elevation range datasets revealed that more than half of grid cells were allocated to more than one subregion. Most of these grid cells were located in areas with a wide range of elevation and/or at the boundaries between subregions. After revising the subregion allocations of eight shifting grid cells, we generated a phylogeny‐ and elevation‐based regionalisation scheme of three regions, comprising eight subregions, for the Sino‐Himalayan flora. Main conclusions By integrating phylogenetic and elevational information, the Sino‐Himalaya can be divided into three floristic regions: the Yunnan Plateau region, the Hengduan Mountains region and the East Himalaya region. Our study provides novel insights into the regionalisation of the flora and highlights the importance of incorporating elevation data in the bioregionalisation of areas with a broad elevational range.

The NDR kinase–MOB complex FgCot1‐Mob2 regulates polarity and lipid metabolism in Fusarium graminearum - Na Liu; Jing Wang; Yingzi Yun; Jinli Wang; Chaoyun Xu; Siqi Wu; Luona Xu; Baohua Li; Ilana Kolodkin‐Gal; Dawood H. Dawood; Youfu Zhao; Zhonghua Ma; et al. (Environmental Microbiology, 2021)
Summary Members of the NDR (nuclear Dbf2‐related) protein‐kinase family are essential for cell differentiation and polarized morphogenesis. However, their functions in plant pathogenic fungi are not well understood. Here, we characterized the NDR kinase FgCot1 and its activator FgMob2 in Fusarium graminearum , a major pathogen causing Fusarium head blight (FHB) in wheat. FgCot1 and FgMob2 formed a NDR kinase–MOB protein complex. Localization assays using FgCot1‐GFP or FgMob2‐RFP constructs showed diverse subcellular localizations, including cytoplasm, septum, nucleus and hyphal tip. Δ Fgcot 1 and Δ Fgmob 2 exhibited serious defects in hyphal growth, polarity, fungal development and cell wall integrity as well as reduced virulence in planta . In contrast, lipid droplet accumulation was significantly increased in these two mutants. Phosphorylation of FgCot1 at two highly conserved residues (S462 and T630) as well as five new sites synergistically contributed its role in various cellular processes. In addition, non‐synonymous mutations in two MAPK (mitogen‐activated protein kinase) proteins, FgSte11 and FgGpmk1, partially rescued the growth defect of Δ Fgmob2 , indicating a functional link between the FgCot1–Mob2 complex and the FgGpmk1 signalling pathway in regulating filamentous fungal growth. These results indicated that the FgCot1–Mob2 complex is critical for polarity, fungal development, cell wall organization, lipid metabolism and virulence in F. graminearum .

Genome-wide association analysis for yield-related traits at the R6 stage in a Chinese soybean mini core collection - Xiangnan Li; Yang Zhou; Yuanpeng Bu; Xinfang Wang; Yumei Zhang; Na Guo; Jinming Zhao; Han Xing (Genes & Genomics, 2021)

Breast cancer organoids from malignant pleural effusion-derived tumor cells as an individualized medicine platform - Bo Pan; Dongyi Zhao; Yaqian Liu; Na Li; Chen Song; Ning Li; Xuelu Li; Zuowei Zhao (In Vitro Cellular & Developmental Biology - Animal, 2021)

Evaluation of the efficacy and safety of hydroxychloroquine in comparison with chloroquine in moderate and severe patients with COVID-19 - Qiuyu Li; Cheng Cui; Fei Xu; Jianping Zhao; Nan Li; Haichao Li; Tianbing Wang; Hua Zhang; Na Liu; Yudong Wei; Xiaoye Niu; Yan Xu; et al. (Science China Life Sciences, 2021)

Nitrogen removal performance and bacterial communities in zeolite trickling filter under different influent C/N ratios - Lina Liu; Na Li; Chunyang Tao; Yubo Zhao; Jingqing Gao; Zhenzhen Huang; Jingshen Zhang; Jianlei Gao; Jinliang Zhang; Ming Cai (Environmental Science and Pollution Research, 2021)

A highly selective and sensitive upconversion nanoprobe for monitoring hydroxyl radicals in living cells and the liver - Guangshun Yu; Na Feng; Dan Zhao; Hao Wang; Yi Jin; Dandan Liu; Zhenhua Li; Xinjian Yang; Kun Ge; Jinchao Zhang (Science China Life Sciences, 2021)

Biomonitoring of heavy metal contamination with roadside trees from metropolitan area of Hefei, China - Ting Fang; Ting Jiang; Kun Yang; Jing Li; Yangyang Liang; Xiuxia Zhao; Na Gao; Hui Li; Wenxuan Lu; Kai Cui (Environmental Monitoring and Assessment, 2021)

Divalent tranylcypromine derivative as lysine-specific demethylase 1 inhibitor - Yin Sun; Na Li; Mingbo Su; Xiaowen Wang; Dongmei Zhao; Bing Xiong; Yubo Zhou; Tongchao Liu; Yue-Lei Chen (Medicinal Chemistry Research, 2021)

NLRP3 inflammasome priming and activation in cholestatic liver injury via the sphingosine 1-phosphate/S1P receptor 2/Gα(12/13)/MAPK signaling pathway - Lei Hou; Zhi Zhang; Le Yang; Na Chang; Xinhao Zhao; Xuan Zhou; Lin Yang; Liying Li (Journal of Molecular Medicine, 2021)

H2S probe CPC inhibits autophagy and promotes apoptosis by inhibiting glutathionylation of Keap1 at Cys434 - Na Li; JuYuan Wang; XiaoLing Zang; ZhaoYang Wang; Tao Zhang; BaoXiang Zhao; JunYing Miao; ZhaoMin Lin (Apoptosis, 2021)

Virtual screening of potentially endocrine-disrupting chemicals against nuclear receptors and its application to identify PPARγ-bound fatty acids - Chaitanya K. Jaladanki; Yang He; Li Na Zhao; Sebastian Maurer-Stroh; Lit-Hsin Loo; Haiwei Song; Hao Fan (Archives of Toxicology, 2021)
Nuclear receptors (NRs) are key regulators of energy homeostasis, body development, and sexual reproduction. Xenobiotics binding to NRs may disrupt natural hormonal systems and induce undesired adverse effects in the body. However, many chemicals of concerns have limited or no experimental data on their potential or lack-of-potential endocrine-disrupting effects. Here, we propose a virtual screening method based on molecular docking for predicting potential endocrine-disrupting chemicals (EDCs) that bind to NRs. For 12 NRs, we systematically analyzed how multiple crystal structures can be used to distinguish actives and inactives found in previous high-throughput experiments. Our method is based on (i) consensus docking scores from multiple structures at a single functional state (agonist-bound or antagonist-bound), (ii) multiple functional states (agonist-bound and antagonist-bound), and (iii) multiple pockets (orthosteric site and alternative sites) of these NRs. We found that the consensus enrichment from multiple structures is better than or comparable to the best enrichment from a single structure. The discriminating power of this consensus strategy was further enhanced by a chemical similarity-weighted scoring scheme, yielding better or comparable enrichment for all studied NRs. Applying this optimized method, we screened 252 fatty acids against peroxisome proliferator-activated receptor gamma (PPARγ) and successfully identified 3 previously unknown fatty acids with Kd = 100–250 μM including two furan fatty acids: furannonanoic acid (FNA) and furanundecanoic acid (FUA), and one cyclopropane fatty acid: phytomonic acid (PTA). These results suggested that the proposed method can be used to rapidly screen and prioritize potential EDCs for further experimental evaluations.

SUMOylation of Pdia3 exacerbates proinsulin misfolding and ER stress in pancreatic beta cells - Na Li; Xi Luo; Qilin Yu; Ping Yang; Zhishui Chen; Xinqiang Wang; Jipin Jiang; Jing Xu; Quan Gong; Decio L. Eizirik; Zhiguang Zhou; Jiajun Zhao; et al. (Journal of Molecular Medicine, 2020)

Correction to: Reduced nNOS activity is responsible for impaired fatty acid–dependent mitochondrial oxygen consumption in atrial myocardium from hypertensive rat - Yu Na Wu; Chun Li Jin; Ji Hyun Jang; Zai Hao Zhao; Sung Joon Kim; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

Reduced nNOS activity is responsible for impaired fatty acid–dependent mitochondrial oxygen consumption in atrial myocardium from hypertensive rat - Yu Na Wu; Chun Li Jin; Ji Hyun Jang; Zai Hao Zhao; Sung Joon Kim; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2020)

In vitro dual-target activities and in vivo antidiabetic effect of 3-hydroxy-N-(p-hydroxy-phenethyl) phthalimide in high-fat diet and streptozotocin-induced diabetic golden hamsters - Bin Xiao; Yunfeng Xiao; Haining Ning; Xiaoyan Han; Wenyan Li; Yuheng Ma; Na Zhao; Guanhua Du; Yu Dong; Jee H. Jung; Zhanfei She (Medicinal Chemistry Research, 2020)

Effects of arbuscular mycorrhizal fungi on redox homeostasis of rice under Cd stress - Hui Li; Xun Wen Chen; Li Wu; Na Luo; Wei Xiong Huang; Ce Hui Mo; Yan Wen Li; Lei Xiang; Hai Ming Zhao; Quan Ying Cai; Ming Hung Wong (Plant and Soil, 2020)

A fundamental theorem for eco-environmental surface modelling and its applications - Tianxiang Yue; Na Zhao; Yu Liu; Yifu Wang; Bin Zhang; Zhengping Du; Zemeng Fan; Wenjiao Shi; Chuanfa Chen; Mingwei Zhao; Dunjiang Song; Shihai Wang; et al. (Science China Earth Sciences, 2020)

Benzophenone glycosides from the pericarps of Aquilaria yunnanensis S. C. Huang - Hui Sun; Yun-Feng Zhang; Hui-Xia Huo; Peng-Wei Guan; Chao-Chao Wang; Hui-Na Yao; Yun-Fang Zhao; Peng-Fei Tu; Jun Li (Natural Product Research, 2020)

Genome-wide identification of the NPR1-like gene family in Brassica napus and functional characterization of BnaNPR1 in resistance to Sclerotinia sclerotiorum - Zheng Wang; Lu-Yue Ma; Xiao Li; Feng-Yun Zhao; Rehman Sarwar; Jun Cao; Yu-Long Li; Li-Na Ding; Ke-Ming Zhu; Yan-Hua Yang; Xiao-Li Tan (Plant Cell Reports, 2020)

Identification and characterization of the melanocortin 1 receptor gene (MC1R) in hypermelanistic Chinese tongue sole (Cynoglossus semilaevis) - Kunming Li; Na Zhao; Bo Zhang; Lei Jia; Kefeng Liu; Qunshan Wang; Xiaoxu He; Baolong Bao (Fish Physiology and Biochemistry, 2020)

Analysis of Myoglobin Stability and Bacterial Community Diversity in Mutton Chop Rolls During Cold Preservation - Xue-Qi Zhang; Tao Jiang; Na Guo; Li Bai; Dong-Mei Zhao (Current Microbiology, 2020)

Do fungal associates of co-occurring orchids promote seed germination of the widespread orchid species Gymnadenia conopsea? - Yue Gao; Zeyu Zhao; Jiayao Li; Na Liu; Hans Jacquemyn; Shunxing Guo; Xiaoke Xing (Mycorrhiza, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Transient Forebrain Ischemia Induces Differential Bdnf Transcript Expression and Histone Acetylation Patterns in the Rat Hippocampus - Jianguo Li; Deping Yan; Na Ma; Jing Chen; Xin Zhao; Yu Zhang; Ce Zhang (Journal of Molecular Neuroscience, 2020)

Design and Synthesis of Polymer Prodrugs for Improving Water-Solubility, Pharmacokinetic Behavior and Antitumor Efficacy of TXA9 - Yiwen Li; Chun Ye; Chengcheng Cai; Meng Zhao; Na Han; Zhihui Liu; Jianxiu Zhai; Jun Yin (Pharmaceutical Research, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Membrane proteomic analysis reveals the intestinal development is deteriorated by intrauterine growth restriction in piglets - Shimeng Huang; Cong Liu; Na Li; Zhenhua Wu; Tiantian Li; Dandan Han; Zhen Li; Jiangchao Zhao; Junjun Wang (Functional & Integrative Genomics, 2020)

Identification and validation of the superior alleles for wheat kernel traits detected by genome-wide association study under different nitrogen environments - Na Zhang; Xilan Zhang; Liqiang Song; Qiannan Su; Shuai Zhang; Jiajia Liu; Wei Zhang; Xiaoyi Fu; Minghui Zhao; Lijing Sun; Jun Ji; Wenchen Qiao; et al. (Euphytica, 2020)

Transient Receptor Potential Ankyrin 1 Contributes to Lysophosphatidylcholine-Induced Intracellular Calcium Regulation and THP-1-Derived Macrophage Activation - Chao Tian; Rongqi Huang; Feng Tang; Zuoxian Lin; Na Cheng; Xiaobo Han; Shuai Li; Peng Zhou; Sihao Deng; Hualin Huang; Huifang Zhao; Junjie Xu; et al. (The Journal of Membrane Biology, 2020)

Maize NCP1 negatively regulates drought and ABA responses through interacting with and inhibiting the activity of transcription factor ABP9 - Na Zong; Hanqian Wang; Zaoxia Li; Li Ma; Li Xie; Junling Pang; Yunliu Fan; Jun Zhao (Plant Molecular Biology, 2020)

The DI–DII linker of human parainfluenza virus type 3 fusion protein is critical for the virus - Ying Liu; Miaomiao Chi; Hongling Wen; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2020)

Stress-dependent anisotropy index of strength and deformability of jointed rock mass: insights from a numerical study - Na Wu; Zheng-zhao Liang; Ying-chun Li; Hong Li; Wan-run Li; Mei-li Zhang (Bulletin of Engineering Geology and the Environment, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

Development of a reverse genetics system for Japanese encephalitis virus strain SA14-14-2 - Guohua Li; Hongli Jin; Xin Nie; Yongkun Zhao; Na Feng; Zongxi Cao; Shuyi Tan; Bo Zhang; Weiwei Gai; Feihu Yan; Ling Li; Ying Zhang; et al. (Virus Genes, 2019)

Methane emissions responding to Azolla inoculation combined with midseason aeration and N fertilization in a double-rice cropping system - Ya-Dong Yang; He-Shui Xu; Deng-Yun Li; Jing-Na Liu; Jiang-Wen Nie; Zhao-Hai Zeng (Environmental Science and Pollution Research, 2019)

Seminal Plasma Exosomes: Promising Biomarkers for Identification of Male and Pseudo-Males in Cynoglossus semilaevis - Bo Zhang; Na Zhao; Lei Jia; Kang Peng; Jinyuan Che; Kunming Li; Xiaoxu He; Jinsheng Sun; Baolong Bao (Marine Biotechnology, 2019)

Transcription profiles reveal the regulatory mechanisms of spur bud changes and flower induction in response to shoot bending in apple (Malus domestica Borkh.) - Libo Xing; Dong Zhang; Siyan Qi; Xilong Chen; Na An; Youmei Li; Caiping Zhao; Mingyu Han; Juan Zhao (Plant Molecular Biology, 2019)

Identification of QTL regions for seedling root traits and their effect on nitrogen use efficiency in wheat (Triticum aestivum L.) - Xiaoli Fan; Wei Zhang; Na Zhang; Mei Chen; Shusong Zheng; Chunhua Zhao; Jie Han; Jiajia Liu; Xilan Zhang; Liqiang Song; Jun Ji; Xigang Liu; et al. (Theoretical and Applied Genetics, 2018)

Sex Differences in Neuropathology and Cognitive Behavior in APP/PS1/tau Triple-Transgenic Mouse Model of Alzheimer’s Disease - Jun-Ting Yang; Zhao-Jun Wang; Hong-Yan Cai; Li Yuan; Meng-Ming Hu; Mei-Na Wu; Jin-Shun Qi (Neuroscience Bulletin, 2018)

Overexpression of Chalcone Isomerase (CHI) Increases Resistance Against Phytophthora sojae in Soybean - Yang Zhou; Jian-li Huang; Xiao-li Zhang; Long-ming Zhu; Xin-fang Wang; Na Guo; Jin-ming Zhao; Han Xing (Journal of Plant Biology, 2018)

Integrity monitoring of high-accuracy GNSS-based attitude determination - Na Li; Lin Zhao; Liang Li; Chun Jia (GPS Solutions, 2018)

Genome-Wide Association Studies of Soybean Seed Hardness in the Chinese Mini Core Collection - Xing Zhang; Jinming Zhao; Yuanpeng Bu; Dong Xue; Zhangxiong Liu; Xiangnan Li; Jing Huang; Na Guo; Haitang Wang; Han Xing; Lijuan Qiu (Plant Molecular Biology Reporter, 2018)

Low dosage of arsenic trioxide (As2O3) inhibits angiogenesis in epithelial ovarian cancer without cell apoptosis - Dehong Luo; Xiaoyuan Zhang; Renle Du; Wenjuan Gao; Na Luo; Shuangtao Zhao; Yi Li; Rui Chen; Hui Wang; Yonghua Bao; Wancai Yang; Daishun Liu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Numerical Investigation of the Effect of Additional Pulmonary Blood Flow on Patient-Specific Bilateral Bidirectional Glenn Hemodynamics - Biao Si; Bin Qiao; Guang Yang; Meng Zhu; Fengyu Zhao; Tongjian Wang; Na Li; Xiaopeng Ji; Guanghong Ding (Cardiovascular Engineering and Technology, 2018)

Functional analysis of amino acids at stalk/head interface of human parainfluenza virus type 3 hemagglutinin-neuraminidase protein in the membrane fusion process - Jingjing Jiang; Hongling Wen; Miaomiao Chi; Ying Liu; Jingxue Liu; Zhankui Cao; Li Zhao; Yanyan Song; Na Liu; Lianli Chi; Zhiyu Wang (Virus Genes, 2018)

Methylation of secreted frizzled-related protein 1 (SFRP1) promoter downregulates Wnt/β-catenin activity in keloids - Jiaqi Liu; Huayu Zhu; Hongtao Wang; Jun Li; Fu Han; Yang Liu; Wanfu Zhang; Ting He; Na Li; Zhao Zheng; Dahai Hu (Journal of Molecular Histology, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

A new arbutin derivative from the leaves of Vaccinium dunalianum wight - Na Li; Wei-Lin Zeng; Xu-Lu Luo; Chong-Ren Yang; Ying-Jun Zhang; Yong Ding; Ping Zhao (Natural Product Research, 2018)

Complete mitochondrial genome of the Pleuronichthys lighti (Pleuronectiformes, Pleuronectidae) with phylogenetic consideration - Yaoxuan Song; Na Song; Yongdong Zhou; Pengfei Li; Shujiang Zhao; Tianxiang Gao (Genes & Genomics, 2017)

A new catechin derivative from the fruits of Rosa sterilis S. D. Shi - Xu-Lu Luo; Han-Long Dan; Na Li; Yong-He Li; Ying-Jun Zhang; Ping Zhao (Natural Product Research, 2017)

Locus Mapping, Molecular Cloning, and Expression Analysis of rps6kb2, a Novel Metamorphosis-Related Gene in Chinese Tongue Sole (Cynoglossus semilaevis) - Yang Liu; Min Wei; Hua Guo; Changwei Shao; Liang Meng; Wenteng Xu; Na Wang; Lei Wang; Deborah M Power; Jilun Hou; Shahid Mahboob; Zhongkai Cui; et al. (Marine Biotechnology, 2017)

Kinetics of Antioxidant-Producing Maillard Reaction in the Mixture of Ribose and Sea Cucumber ( Stichopus japonicus ) Gut Hydrolysates - Jia-Run Han; Zhi-Mo Zhu; Hai-Tao Wu; Na Sun; Yue Tang; Cui-Ping Yu; Chen-Chen Zhao; Zheng-Yu Zhang; Ao-Ting Li; Jia-Nan Yan (Journal of Aquatic Food Product Technology, 2017)

Negligible effect of eNOS palmitoylation on fatty acid regulation of contraction in ventricular myocytes from healthy and hypertensive rats - Chun Li Jin; Yu Na Wu; Ji Hyun Jang; Zai Hao Zhao; Goo Taeg Oh; Sung Joon Kim; Yin Hua Zhang (Pflügers Archiv - European Journal of Physiology, 2017)

Macroinvertebrate distribution and aquatic ecology in the Ruoergai (Zoige) Wetland, the Yellow River source region - Na Zhao; Mengzhen Xu; Zhiwei Li; Zhaoyin Wang; Hanmi Zhou (Frontiers of Earth Science, 2017)

Pathogen richness and abundance predict patterns of adaptive major histocompatibility complex variation in insular amphibians - Supen Wang; Conghui Liu; Anthony B. Wilson; Na Zhao; Xianping Li; Wei Zhu; Xu Gao; Xuan Liu; Yiming Li (Molecular Ecology, 2017)
The identification of the factors responsible for genetic variation and differentiation at adaptive loci can provide important insights into the evolutionary process and is crucial for the effective management of threatened species. We studied the impact of environmental viral richness and abundance on functional diversity and differentiation of the MHC class Ia locus in populations of the black‐spotted pond frog ( Pelophylax nigromaculatus ), an IUCN ‐listed species, on 24 land‐bridge islands of the Zhoushan Archipelago and three nearby mainland sites. We found a high proportion of private MHC alleles in mainland and insular populations, corresponding to 32 distinct functional supertypes, and strong positive selection on MHC antigen‐binding sites in all populations. Viral pathogen diversity and abundance were reduced at island sites relative to the mainland, and islands housed distinctive viral communities. Standardized MHC diversity at island sites exceeded that found at neutral microsatellites, and the representation of key functional supertypes was positively correlated with the abundance of specific viruses in the environment ( Frog virus 3 and Ambystoma tigrinum virus ). These results indicate that pathogen‐driven diversifying selection can play an important role in maintaining functionally important MHC variation following island isolation, highlighting the importance of considering functionally important genetic variation and host–pathogen associations in conservation planning and management.

Spatial and temporal changes in desertification in the southern region of the Tengger Desert from 1973 to 2009 - Qingyu Guan; Wenqian Guan; Jing Yang; Shilei Zhao; Baotian Pan; Lei Wang; Na Song; Min Lu; Fuchun Li (Theoretical and Applied Climatology, 2017)

Transcriptional and Biochemical Alterations in Zebrafish Eleuthero-Embryos (Danio rerio) After Exposure to Synthetic Progestogen Dydrogesterone - Wen-Jun Shi; Guang-Guo Ying; Guo-Yong Huang; Yan-Qiu Liang; Li-Xin Hu; Jian-Liang Zhao; Jin-Na Zhang (Bulletin of Environmental Contamination and Toxicology, 2017)

Characterization of the temporal and spatial expression of wheat (Triticum aestivum L.) plant height at the QTL level and their influence on yield-related traits - Na Zhang; Xiaoli Fan; Fa Cui; Chunhua Zhao; Wei Zhang; Xueqiang Zhao; Lijuan Yang; Ruiqing Pan; Mei Chen; Jie Han; Jun Ji; Dongcheng Liu; et al. (Theoretical and Applied Genetics, 2017)

Identification and characterization of PyAQPs from Pyropia yezoensis, which are involved in tolerance to abiotic stress - Fanna Kong; Junqing Yang; Na Li; Hailong Zhao; Yunxiang Mao (Journal of Applied Phycology, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Construction of Plastid Expression Vector and Development of Genetic Transformation System for the Seaweed Pyropia yezoensis - Fanna Kong; Hailong Zhao; Weixun Liu; Na Li; Yunxiang Mao (Marine Biotechnology, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

RNA-Seq Analysis of the Antioxidant Status and Immune Response of Portunus trituberculatus Following Aerial Exposure - Yuquan Li; Shoumin Lai; Renjie Wang; Yuchao Zhao; Hao Qin; Lingxu Jiang; Na Li; Qiang Fu; Chao Li (Marine Biotechnology, 2017)

Historical introduction, geographical distribution, and biological characteristics of alien plants in China - Chao Chen; Qing-Hai Wang; Ju-Ying Wu; Ding Huang; Wei-Hua Zhang; Na Zhao; Xue-Feng Li; Li-Xue Wang (Biodiversity and Conservation, 2017)

HuR mediates motility of human bone marrow-derived mesenchymal stem cells triggered by sphingosine 1-phosphate in liver fibrosis - Na Chang; Jingjing Ge; Lei Xiu; Zhongxin Zhao; Xianghui Duan; Lei Tian; Jieshi Xie; Lin Yang; Liying Li (Journal of Molecular Medicine, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Therapeutic effects of histone deacetylase inhibitors in a murine asthma model - Yuan Ren; Xinming Su; Lingfei Kong; Menglu Li; Xuan Zhao; Na Yu; Jian Kang (Inflammation Research, 2016)

Different responses of soybean cyst nematode resistance between two RIL populations derived from Peking × 7605 under two ecological sites - YONGCHUN LI; NA GUO; JINMING ZHAO; BIN ZHOU; RAN XU; HUI DING; WEIGUO ZHAO; JUNYI GAI; HAN XING (Journal of Genetics, 2016)

Urban expansion in China and its effect on cultivated land before and after initiating “Reform and Open Policy” - ZengXiang Zhang; QingKe Wen; Fang Liu; XiaoLi Zhao; Bin Liu; JinYong Xu; Ling Yi; ShunGuang Hu; Xiao Wang; LiJun Zuo; Na Li; MinMin Li; et al. (Science China Earth Sciences, 2016)

Genome-wide study refines the quantitative trait locus for number of ribs in a Large White × Minzhu intercross pig population and reveals a new candidate gene - Long-Chao Zhang; Jing-Wei Yue; Lei Pu; Li-Gang Wang; Xin Liu; Jing Liang; Hua Yan; Ke-Bin Zhao; Na Li; Hui-Bi Shi; Yue-Bo Zhang; Li-Xian Wang (Molecular Genetics and Genomics, 2016)

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice - Xiaoru Long; Jun Xie; Keting Zhao; Wei Li; Wei Tang; Sisi Chen; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Lijia Wang; Zhou Fu; et al. (Medical Microbiology and Immunology, 2016)

Syntheses, properties and bio-activities of water-soluble CO-releasing molecule based on manganese - Taofeng Zhang; Meng Li; Yaguo Gong; Na Xi; Yawen Zheng; Quanyi Zhao; Yonglin Chen; Bin Liu (JBIC Journal of Biological Inorganic Chemistry, 2016)

Urban expansion in China and its spatial-temporal differences over the past four decades - Fang Liu; Zengxiang Zhang; Lifeng Shi; Xiaoli Zhao; Jinyong Xu; Ling Yi; Bin Liu; Qingke Wen; Shunguang Hu; Xiao Wang; Lijun Zuo; Na Li; et al. (Journal of Geographical Sciences, 2016)

Sirtuin-3 (SIRT3) protects pancreatic β-cells from endoplasmic reticulum (ER) stress-induced apoptosis and dysfunction - Hao-Hao Zhang; Xiao-Jun Ma; Li-Na Wu; Yan-Yan Zhao; Peng-Yu Zhang; Ying-Hui Zhang; Ming-Wei Shao; Fei Liu; Fei Li; Gui-Jun Qin (Molecular and Cellular Biochemistry, 2016)

Prognostic significance of FLT3-ITD in pediatric acute myeloid leukemia: a meta-analysis of cohort studies - Xiaoli Wu; Xuefeng Feng; Xiaoqing Zhao; Futian Ma; Na Liu; Hongming Guo; Chaonan Li; Huan Du; Baoxi Zhang (Molecular and Cellular Biochemistry, 2016)

The effect of immunosuppressive drug cyclosporine A on myeloid-derived suppressor cells in transplanted mice - Chenlu Han; Tingting Wu; Ning Na; Yang Zhao; Weiguo Li; Yong Zhao (Inflammation Research, 2016)

[Gly14]-Humanin Protects Against Amyloid β Peptide-Induced Impairment of Spatial Learning and Memory in Rats - Li Yuan; Xiao-Jie Liu; Wei-Na Han; Qing-Shan Li; Zhao-Jun Wang; Mei-Na Wu; Wei Yang; Jin-Shun Qi (Neuroscience Bulletin, 2016)

TNFα-induced M-MDSCs promote transplant immune tolerance via nitric oxide - Fan Yang; Yang Li; Tingting Wu; Ning Na; Yang Zhao; Weiguo Li; Chenlu Han; Lianfeng Zhang; Jun Lu; Yong Zhao (Journal of Molecular Medicine, 2016)

Complement receptor activity of recombinant porcine CR1-like protein expressed in a eukaryotic system - Wei Yin; Xiaoming Wei; Junbing Jiang; Kuohai Fan; Junxing Zhao; Na Sun; Zhiwei Wang; Yaogui Sun; Haili Ma; Xin Zhao; Hongquan Li (Immunologic Research, 2016)

Reverse transcription genome exponential amplification reaction assay for rapid and universal detection of human rhinoviruses - Li Guan; Lin-Qing Zhao; Hang-Yu Zhou; Kai Nie; Xin-Na Li; Dan Zhang; Juan Song; Yuan Qian; Xue-Jun Ma (Archives of Virology, 2016)

Loci and candidate gene identification for resistance to Phytophthora sojae via association analysis in soybean [Glycine max (L.) Merr.] - Lihong Li; Na Guo; Jingping Niu; Zili Wang; Xiaoxia Cui; Jutao Sun; Tuanjie Zhao; Han Xing (Molecular Genetics and Genomics, 2016)

Interferon-inducible GTPase: a novel viral response protein involved in rabies virus infection - Ling Li; Hualei Wang; Hongli Jin; Zengguo Cao; Na Feng; Yongkun Zhao; Xuexing Zheng; Jianzhong Wang; Qian Li; Guoxing Zhao; Feihu Yan; Lina Wang; et al. (Archives of Virology, 2016)

Visual detection of Ebola virus using reverse transcription loop-mediated isothermal amplification combined with nucleic acid strip detection - Changping Xu; Hualei Wang; Hongli Jin; Na Feng; Xuexing Zheng; Zengguo Cao; Ling Li; Jianzhong Wang; Feihu Yan; Lina Wang; Hang Chi; Weiwei Gai; et al. (Archives of Virology, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Eimeria tenella: a novel dsRNA virus in E. tenella and its complete genome sequence analysis - Bin Wu; Xichen Zhang; Pengtao Gong; Mingying Li; He Ding; Caiyan Xin; Na Zhao; Jianhua Li (Virus Genes, 2016)

Extraction of basic trends of urban expansion in China over past 40 years from satellite images - Qingke Wen; Zengxiang Zhang; Lifeng Shi; Xiaoli Zhao; Fang Liu; Jinyong Xu; Ling Yi; Bin Liu; Xiao Wang; Lijun Zuo; Shunguang Hu; Na Li; et al. (Chinese Geographical Science, 2016)

QTL detection for wheat kernel size and quality and the responses of these traits to low nitrogen stress - Fa Cui; Xiaoli Fan; Mei Chen; Na Zhang; Chunhua Zhao; Wei Zhang; Jie Han; Jun Ji; Xueqiang Zhao; Lijuan Yang; Zongwu Zhao; Yiping Tong; et al. (Theoretical and Applied Genetics, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Isolation and sequence analysis of the complete NS1 and VP2 genes of canine parvovirus from domestic dogs in 2013 and 2014 in China - Hualei Wang; Hongli Jin; Qian Li; Guoxing Zhao; Nan Cheng; Na Feng; Xuexing Zheng; Jianzhong Wang; Yongkun Zhao; Ling Li; Zengguo Cao; Feihu Yan; et al. (Archives of Virology, 2016)

Cotton mitogen-activated protein kinase4 (GhMPK4) confers the transgenic Arabidopsis hypersensitivity to salt and osmotic stresses - Na-Na Wang; Li–Li Zhao; Rui Lu; Yang Li; Xue-Bao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Identification and genetic characterization of two porcine astroviruses from domestic piglets in China - Jin-song Li; Mao-zhong Li; Li-shu Zheng; Na Liu; Dan-di Li; Zhao-jun Duan (Archives of Virology, 2015)

Recursive impedance inversion of ground-penetrating radar data in stochastic media - Zhao-Fa Zeng; Xiong Chen; Jing Li; Ling-Na Chen; Qi Lu; Feng-Shan Liu (Applied Geophysics, 2015)

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′- O -caffeoylarbutin in different parts of Vaccinium dunalianum Wight - Xu-Lu Luo; Na Li; Min Xu; Hong-Tao Zhu; Peng He; Yong Ding; Ping Zhao; Ying-Jun Zhang (Natural Product Research, 2015)

Inhibitory effect of totarol on exotoxin proteins hemolysin and enterotoxins secreted by Staphylococcus aureus - Ce Shi; Xingchen Zhao; Wenli Li; Rizeng Meng; Zonghui Liu; Mingyuan Liu; Na Guo; Lu Yu (World Journal of Microbiology and Biotechnology, 2015)

Retraction Note to: Construction of pancreatic cancer double-factor regulatory network based on chip data on the transcriptional level - Li-Li Zhao; Tong Zhang; Bing-Rong Liu; Tie-Fu Liu; Na Tao; Li-Wei Zhuang (Molecular Biology Reports, 2015)

Knockdown of PFTK1 Inhibits the Migration of Glioma Cells - Shaochen Fan; Chengjin Zhao; Li Zhang; Shirong Dai; Jianbing Ren; Xiubing Zhang; Na Ban; Xiaojuan He; Lixiang Yang; Zhen Bao; Wenjuan Chen; Jie Sun; et al. (Journal of Molecular Neuroscience, 2015)

Responses of carbon transfer, partitioning, and residence time to land use in the plant–soil system of an alpine meadow on the Qinghai-Tibetan Plateau - Liang Zhao; Dongdong Chen; Na Zhao; Qi Li; Qian Cheng; Caiyun Luo; Shixiao Xu; Shiping Wang; Xinquan Zhao (Biology and Fertility of Soils, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Characterization of important odorants in four steamed Coilia ectenes from China by gas chromatography–mass spectrometry–olfactometry - Lin-min Zhao; Wei Wu; Ning-ping Tao; Yu-qi Li; Na Wu; Xiao Qin (Fisheries Science, 2015)

Geographic and genetic identification of RppS, a novel locus conferring broad resistance to southern corn rust disease in China - Xiaojun Wu; Na Li; Panfeng Zhao; Yan He; Shoucai Wang (Euphytica, 2015)

Isolation of differentially expressed sex genes in garden asparagus using suppression subtractive hybridization - Chuan-liang Deng; Ning-na Wang; Shu-fen Li; Tian-yu Dong; Xin-peng Zhao; Shao-jing Wang; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2015)

LYG-202 exerts antitumor effect on PI3K/Akt signaling pathway in human breast cancer cells - Yue Zhao; Xiaoping Wang; Yang Sun; Yuxin Zhou; Yuehan Yin; Youxiang Ding; Zhiyu Li; Qinglong Guo; Na Lu (Apoptosis, 2015)

Notch3/Akt signaling contributes to OSM-induced protection against cardiac ischemia/reperfusion injury - Mingming Zhang; Chen Wang; Jianqiang Hu; Jie Lin; Zhijing Zhao; Min Shen; Haokao Gao; Na Li; Min Liu; Pengfei Zheng; Cuiting Qiu; Erhe Gao; et al. (Apoptosis, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Potential probiotic attributes of a new strain of Bacillus coagulans CGMCC 9951 isolated from healthy piglet feces - Shao-Bin Gu; Li-Na Zhao; Ying Wu; Shi-Chang Li; Jian-Rui Sun; Jing-Fang Huang; Dan-Dan Li (World Journal of Microbiology and Biotechnology, 2015)

Rapid emergence of a PB2-E627K substitution confers a virulent phenotype to an H9N2 avian influenza virus during adaption in mice - Xiaoyu Sang; Airong Wang; Tongjie Chai; Xijun He; Jie Ding; Xiaolong Gao; Yuanguo Li; Kun Zhang; Zhiguang Ren; Lin Li; Zhijun Yu; Tiecheng Wang; et al. (Archives of Virology, 2015)

Using rabies virus vaccine strain SRV9 as viral vector to express exogenous gene - Hualei Wang; Hongli Jin; Na Feng; Xuexing Zheng; Ling Li; Yinglin Qi; Meng Liang; Yongkun Zhao; Tiecheng Wang; Yuwei Gao; Changchun Tu; Ningyi Jin; et al. (Virus Genes, 2015)

Up-regulation of integrin α6β4 expression by mitogens involved in dairy cow mammary development - Feng Zhao; Chang Liu; Yu-Meng Hao; Bo Qu; Ying-Jun Cui; Na Zhang; Xue-Jun Gao; Qing-Zhang Li (In Vitro Cellular & Developmental Biology - Animal, 2015)

Deep water distribution and transport in the Nordic seas from climatological hydrological data - Yan He; Jinping Zhao; Na Liu; Zexun Wei; Yahao Liu; Xiang Li (Acta Oceanologica Sinica, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

Rapid evaluation of reference evapotranspiration in Northern China - Shao-hua Zhao; Yong-hui Yang; Feng Zhang; Xin-xin Sui; Yun-jun Yao; Na Zhao; Qiuxiao Zhao; Chun-qiang Li (Arabian Journal of Geosciences, 2015)

Chinese herbal medicine formula Tao Hong Si Wu decoction protects against cerebral ischemia–reperfusion injury via PI3K/Akt and the Nrf2 signaling pathway - Li Li; Na Yang; Ling Nin; Zhilong Zhao; Lu Chen; Jie Yu; Zhuyun Jiang; Zhendong Zhong; Daiwen Zeng; Hongyi Qi; Xiaoyu Xu (Journal of Natural Medicines, 2015)

Simultaneous determination by UPLC-MS/MS of seven bioactive compounds in rat plasma after oral administration of Ginkgo biloba tablets: application to a pharmacokinetic study - Wen-ping Wang; Na Liu; Qian Kang; Pei-pei Du; Yi Lan; Bo-chen Zhao; Yan-yan Chen; Qing Zhang; Hui Li; Ye-wen Zhang; Qing Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Synthesis, biological evaluation, and molecular docking studies of pyrazolyl-acylhydrazone derivatives as novel anticancer agents - Man Xing; Ting-Ting Zhao; Yu-Jia Ren; Na-Na Peng; Xian-Hui Yang; Xi Li; Hui Zhang; Gao-Qi Liu; Li-Rong Zhang; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

RETRACTED ARTICLE: Construction of pancreatic cancer double-factor regulatory network based on chip data on the transcriptional level - Li-Li Zhao; Tong Zhang; Bing-Rong Liu; Tie-Fu Liu; Na Tao; Li-Wei Zhuang (Molecular Biology Reports, 2014)

Genetic analysis and fine mapping of RpsJS, a novel resistance gene to Phytophthora sojae in soybean [Glycine max (L.) Merr.] - Jutao Sun; Lihong Li; Jinming Zhao; Jing Huang; Qiang Yan; Han Xing; Na Guo (Theoretical and Applied Genetics, 2014)

Identifying novel salt-tolerant genes from Dunaliella salina using a Haematococcus pluvialis expression system - Wen-fang Gong; Li-na Zhao; Bin Hu; Xi-wen Chen; Feng Zhang; Zheng-mao Zhu; De-fu Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Is there a role of TNFR1 in acute lung injury cases associated with extracorporeal circulation? - Yu Zhao; Chong-wei Zhang; Wen-jing Zhou; Jiao Chen; Nan-fu Luo; Li-na Gong; Lei Du; Jing Zhou (Journal of Zhejiang University-SCIENCE B, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Synthesis and analgesic evaluation of a series of proline-typed spiro cyclic quaternary ammoniums - Songwen Lin; Na Wang; Shuo Zhao; Qi Sun; Weiwei Zhang; Jia Ye; Tieming Cheng; Runtao Li (Medicinal Chemistry Research, 2014)

Cloning and expression patterns of the brine shrimp (Artemia sinica) glycogen phosphorylase (GPase) gene during development and in response to temperature stress - Na Zhao; Ming Hou; Ting Wang; Yifei Chen; Ying Lv; Zengrong Li; Rui Zhang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Dishevelled-1 (Dvl-1) Protein: a Potential Participant of Oxidative Stress Induced by Selenium Deficiency - Han-dong Zhao; Mei-na Sun; Meng-di Li; Feng-lan Li; Hui Li (Biological Trace Element Research, 2014)

Structure and dynamics of the bacterial communities in fermentation of the traditional Chinese post-fermented pu-erh tea revealed by 16S rRNA gene clone library - Ming Zhao; Wei Xiao; Yan Ma; Tingting Sun; Wenxia Yuan; Na Tang; Donglian Zhang; Yongxia Wang; Yali Li; Hongjie Zhou; Xiaolong Cui (World Journal of Microbiology and Biotechnology, 2013)

The HTLV-1 HBZ protein inhibits cyclin D1 expression through interacting with the cellular transcription factor CREB - Yunyun Ma; Shangen Zheng; Yuanyuan Wang; Wenqiao Zang; Min Li; Na Wang; Ping Li; Jing Jin; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

An exploratory analysis of benthic macroinvertebrates as indicators of the ecological status of the Upper Yellow and Yangtze Rivers - Baozhu Pan; Zhaoyin Wang; Zhiwei Li; Guo-an Yu; Mengzhen Xu; Na Zhao; Gary Brierley (Journal of Geographical Sciences, 2013)

Differences of DNA methylation profiles between monozygotic twins’ blood samples - Chengtao Li; Shumin Zhao; Na Zhang; Suhua Zhang; Yiping Hou (Molecular Biology Reports, 2013)

Climate change trend in China, with improved accuracy - Tian-Xiang Yue; Na Zhao; R. Douglas Ramsey; Chen-Liang Wang; Ze-Meng Fan; Chuan-Fa Chen; Yi-Min Lu; Bai-Lian Li (Climatic Change, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

Glacial expansion and diversification of an East Asian montane bird, the green‐backed tit ( Parus monticolus ) - Wenjuan Wang; Bailey D. McKay; Chuanyin Dai; Na Zhao; Ruiying Zhang; Yanhua Qu; Gang Song; Shou‐Hsien Li; Wei Liang; Xiaojun Yang; Eric Pasquet; Fumin Lei (Journal of Biogeography, 2013)
Aim We combined genetic sequence data and ecological niche modelling to resolve the impacts of past climatic fluctuations on the distribution, genetic diversification, and demographic dynamics of an East Asian montane bird, the green‐backed tit ( Parus monticolus ). Location East Asia. Methods Phylogenetic analyses were carried out using four mitochondrial fragments and seven nuclear loci from 161 birds sampled from 29 localities spanning the entire geographical range of the green‐backed tit. We used * beast to estimate the species tree and calculate divergence times. Extended Bayesian skyline plots were used to infer potential historical shifts in population size. We used MaxEnt to predict potential distributions during three periods: the present day, the Last Glacial Maximum and the Last Interglacial. Results The mitochondrial DNA (mt DNA ) gene tree showed strong support for three reciprocally monophyletic groups: a south‐western clade, a central clade and a Taiwanese clade. Taiwanese and Vietnamese samples had fixed differences at several nuclear loci, but the south‐western and central samples shared haplotypes at all nuclear loci. The mt DNA gene tree topology differed from the species tree topology. The species tree suggested sister relationships between Taiwanese and Vietnamese operational taxonomic units ( OTU s) and between south‐western and central OTU s. Diversification within the green‐backed tit was relatively recent, probably within the last 0.9 million years. Extended Bayesian skyline plots suggested rapid population expansion in the south‐western and central phylogroups after the Last Interglacial, and this result was consistent with ecological niche models. Main conclusions Our results suggest that genetic diversification within the green‐backed tit was affected by the later Pleistocene climate fluctuations. Ecological niche models indicated that the present‐day vegetation distribution was, in many ways, more similar to that of the Last Glacial Maximum than it was to that of the Last Interglacial. Continental populations of the green‐backed tit experienced unusual demographic and range expansion that is likely to have occurred during the cooling transition between the Last Interglacial and the Last Glacial Maximum. We found incongruence between the mt DNA gene tree and the species tree, which underscores the importance of using both mitochondrial and nuclear markers when estimating the evolutionary history of populations.

Down-regulation of DNA methyltransferase 3B in staurosporine-induced apoptosis and its mechanism in human hepatocarcinoma cell lines - Chao Zhao; Peng Yin; Chuanzhong Mei; Na Li; Wantong Yao; Xin Li; Jingjing Qi; Kun Fan; Zengxia Li; Liying Wang; Yinghong Shi; Shuangjian Qiu; et al. (Molecular and Cellular Biochemistry, 2013)

Chemical characteristics and anticoagulant activities of two sulfated polysaccharides from Enteromorpha linza (Chlorophyta) - Xiaohui Qi; Wenjun Mao; Yin Chen; Yanli Chen; Chunqi Zhao; Na Li; Chunyan Wang (Journal of Ocean University of China, 2013)

DNA polymerase beta promoter mutations affect gene transcription, translation and the sensitivity of esophageal cancer cells to cisplatin treatment - Tao Wang; Wenqiao Zang; Yunyun Ma; Min Li; Xiaoyan Xuan; Na Wang; Rui Wu; Yuebai Li; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

Small water clusters stimulate microcystin biosynthesis in cyanobacterial Microcystis aeruginosa - Jing Wang; Feng Zhao; Baihua Chen; Yanni Li; Ping Na; Jian Zhuo (Journal of Applied Phycology, 2013)

Molecular characterization of influenza B viruses isolated in east-central China in 2009–2010 - Na Zhu; Peng Li; Jingfeng Yu; Yongdong Li; Jiuru Zhao; Han Xia; Shuang Tang; Zhong Zhang; Zheng Kou; Shiyu Yin; Zhaojun Fan; Tianxian Li (Virus Genes, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

QTL detection for node of first fruiting branch and its height in upland cotton (Gossypium hirsutum L.) - Chengqi Li; Changbiao Wang; Na Dong; Xiaoyun Wang; Haihong Zhao; Richard Converse; Zhe Xia; Rui Wang; Qinglian Wang (Euphytica, 2012)

Numerical modeling of PP- and PS-wave azimuthal anisotropy in HTI media - Zhong-Ping Qian; Shao-Hua Zhang; Bo Zhao; Na Lei; Xiang-Yang Li (Applied Geophysics, 2012)

Synthesis, crystal structure and biological activity of novel anthranilic diamide insecticide containing alkyl ether group - Yu Zhao; Li-ping Xu; Jun Tong; Yong-qiang Li; Li-xia Xiong; Fang Li; Li-na Peng; Zheng-ming Li (Molecular Diversity, 2012)

Benfotiamine prevents increased β-amyloid production in HEK cells induced by high glucose - Xiao-Jing Sun; Lei Zhao; Na Zhao; Xiao-Li Pan; Guo-Qiang Fei; Li-Rong Jin; Chun-Jiu Zhong (Neuroscience Bulletin, 2012)

Spatiotemporal patterns and essential role of TNF receptor-associated factor 5 expression after rat spinal cord Injury - Weipeng Huan; Xiujie Wu; Shuangwei Zhang; Yin Zhao; Hua Xu; Na Wang; Honghui Li; Hailei Chen; Haixiang Wei; Youhua Wang (Journal of Molecular Histology, 2012)

Effect of exercise training volume on arterial contractility and BKCa channel activity in rat thoracic aorta smooth muscle cells - Lijun Shi; Li Zhao; Fanxing Zeng; Na Li; Xiaodong Liu (European Journal of Applied Physiology, 2012)

An effective approach for land-cover classification from airborne lidar fused with co-registered data - Yang Cao; Hong Wei; Huijie Zhao; Na Li (International Journal of Remote Sensing, 2012)

Individual and combined effects of MDM2 SNP309 and TP53 Arg72Pro on breast cancer risk: an updated meta-analysis - Hongtao Cheng; Biao Ma; Ran Jiang; Wei Wang; Hui Guo; Na Shen; Dapeng Li; Qunzi Zhao; Rui Wang; Pengfei Yi; Yue Zhao; Zeming Liu; et al. (Molecular Biology Reports, 2012)

Highly efficient decolorization of Malachite Green by a novel Micrococcus sp. strain BD15 - Lin-Na Du; Ming Zhao; Gang Li; Xiao-Ping Zhao; Yu-Hua Zhao (Environmental Science and Pollution Research, 2012)

Enhanced Anti-Diabetic Activity of a Combination of Chromium(III) Malate Complex and Propolis and its Acute Oral Toxicity Evaluation - Xiang-Yang Wu; Fang Li; Ting Zhao; Guang-Hua Mao; Jing Li; Hong-Yuan Qu; Yue-Na Ren; Liu-Qing Yang (Biological Trace Element Research, 2012)

Improving the discrimination capability of bioaerosols using a dual-channel ultraviolet aerodynamic particle sizer spectrometer - Xiao-Ling Ma; Wei-Xiong Zhao; Jia-Qiang Zhao; Na Li; Hai-Yang Zheng; Li Fang; Fei-Hu Chen; Wei-Jun Zhang (Aerobiologia, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Bacterial expression of antigenic sites A and D in the spike protein of transmissible gastroenteritis virus and evaluation of their inhibitory effects on viral infection - Fandan Meng; Zeping Zhao; Guangxing Li; Siqingaowa Suo; Na Shi; Jiechao Yin; Dante Zarlenga; Xiaofeng Ren (Virus Genes, 2011)

Quantitative analysis of expression of six BmGST genes in silkworm, Bombyx mori - Guo-dong Zhao; Yi-ling Zhang; Rui-na Gao; Rui-xian Wang; Ting Zhang; Bing Li; Yi Zhang; Chang-de Lu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Influence of temperature and medium on viability of Demodex folliculorum and Demodex brevis (Acari: Demodicidae) - Ya-E Zhao; Na Guo; Li-Ping Wu (Experimental and Applied Acarology, 2011)

Estimation of cancer cases and deaths attributable to infection in China - Wang Xiang; Ju-Fang Shi; Ping Li; Jian-Bing Wang; Li-Na Xu; Wen-Qiang Wei; Fang-Hui Zhao; You-Lin Qiao; Paolo Boffetta (Cancer Causes & Control, 2011)

Supplemental Selenium Alleviates the Toxic Effects of Excessive Iodine on Thyroid - Jian Xu; Xiao-Li Liu; Xue-Feng Yang; Huai-Lan Guo; Li-na Zhao; Xiu-Fa Sun (Biological Trace Element Research, 2011)

The Mechanism of Liver Injury in Mice Caused by Lanthanoids - Min Fei; Na Li; Yuguan Ze; Jie Liu; Sisi Wang; Xiuaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

Trace analysis of persistent toxic substances in the main stream of Jiangsu section of the Yangtze River, China - Huan He; Guan-jiu Hu; Cheng Sun; Su-lan Chen; Ming-na Yang; Juan Li; Yong Zhao; Hui Wang (Environmental Science and Pollution Research, 2011)

P38-Nrf-2 Signaling Pathway of Oxidative Stress in Mice Caused by Nanoparticulate TiO2 - Jue Wang; Na Li; Lei Zheng; Sisi Wang; Ying Wang; Xiaoyang Zhao; Yanmei Duan; Yaling Cui; Min Zhou; Jingwei Cai; Songjie Gong; Han Wang; et al. (Biological Trace Element Research, 2011)

Microarray Analysis of the Chelerythrine-Induced Transcriptome of Mycobacterium tuberculosis - Junchao Liang; Fanli Zeng; Aizhen Guo; Liqiang Liu; Na Guo; Lei Li; Jing Jin; Xiuping Wu; Mingyuan Liu; Dan Zhao; Yang Li; Qi Jin; et al. (Current Microbiology, 2011)

Biodegradation of malachite green by Pseudomonas sp. strain DY1 under aerobic condition: characteristics, degradation products, enzyme analysis and phytotoxicity - Lin-Na Du; Sheng Wang; Gang Li; Bing Wang; Xiao-Ming Jia; Yu-Hua Zhao; Yun-Long Chen (Ecotoxicology, 2011)

A new stochastic approach to multi-compartment pharmacokinetic models: probability of traveling route and distribution of residence time in linear and nonlinear systems - Liang Zhao; Na Li; Harry Yang (Journal of Pharmacokinetics and Pharmacodynamics, 2011)

Oxidative Stress in the Liver of Mice Caused by Intraperitoneal Injection with Lanthanoides - Min Fei; Na Li; Yuguan Ze; Jie Liu; Xiaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

Cloning and expression of P450c17-I (17α-hydroxylase/17,20-lyase) in brain and ovary during gonad development in Cynoglossus semilaevis - Cai F. Chen; Hai S. Wen; Zhao P. Wang; Feng He; Jia R. Zhang; Xiao Y. Chen; Guo X. Jin; Bao Shi; Dan Shi; Yan P. Yang; Ji F. Li; Bao X. Qi; et al. (Fish Physiology and Biochemistry, 2010)

Callus induction and high-efficiency plant regeneration via somatic embryogenesis in Papaver nudicaule L., an ornamental medicinal plant - Jing Li Yang; Bo Zhao; Eun Soo Seong; Myong Jo Kim; Won Hee Kang; Na Young Kim; Chang Yeon Yu; Cheng Hao Li (Plant Biotechnology Reports, 2010)

Genetic Analysis and Molecular Mapping of a Novel Gene Conferring Resistance to Rice Stripe Virus - Feng Zhao; Zhijun Cai; Tiezhu Hu; Haigen Yao; Li Wang; Na Dong; Bin Wang; Zhengang Ru; Wenxue Zhai (Plant Molecular Biology Reporter, 2010)

Structural basis for the decrease in the outward potassium channel current induced by lanthanum - Li Hong Wang; Na Jiang; Bo Zhao; Xiao Dong Li; Tian Hong Lu; Xiao Lan Ding; Xiao Hua Huang (JBIC Journal of Biological Inorganic Chemistry, 2010)

Effects of Manganese Deficiency on Spectral Characteristics and Oxygen Evolution in Maize Chloroplasts - Xiaolan Gong; Ying Wang; Chao Liu; Sisi Wang; Xiaoyang Zhao; Min Zhou; Na Li; Yun Lu; Fashui Hong (Biological Trace Element Research, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Determining the filtration efficiency of half-face medical protection mask (N99) against viral aerosol - ZhanBo Wen; JianChun Lu; JinSong Li; Na Li; JianJun Zhao; Jie Wang; Long Yu; WenHui Yang (Aerobiologia, 2010)

Fluorescent Property of the Gd3+-Doped Terbium Complexes and Crystal Structure of [Tb(TPTZ)(H2O)6]Cl3·3H2O - Yan-Fang Zhao; Yong-Liang Zhao; Feng Bai; Xiao-yan Wei; Yong-sheng Zhou; Mei-na Shan; Huan-huan Li; Rui-jun Ma; Xiao-tao Fu; Yan Du (Journal of Fluorescence, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Reciprocal regulation between M3 muscarinic acetylcholine receptor and protein kinase C-ε in ventricular myocytes during myocardial ischemia in rats - Peng-zhou Hang; Jing Zhao; Yu-ping Wang; Li-hua Sun; Yong Zhang; Li-li Yang; Na Zhao; Zhi-dan Sun; Yu-ying Mao; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Detection of viral aerosols by use of real-time quantitative PCR - Zhanbo Wen; Long Yu; Wenhui Yang; Jie Wang; Jianjun Zhao; Na Li; Jianchun Lu; Jinsong Li (Aerobiologia, 2009)

Impact of Waterborne Copper on the Structure of Gills and Hepatopancreas and its Impact on the Content of Metallothionein in Juvenile Giant Freshwater Prawn Macrobrachium rosenbergii (Crustacea: Decapoda) - Na Li; Yunlong Zhao; Jian Yang (Archives of Environmental Contamination and Toxicology, 2009)

Identifying wetland change in China’s Sanjiang Plain using remote sensing - Shuqing Zhang; Xiaodong Na; Bo Kong; Zongming Wang; Hongxing Jiang; Huan Yu; Zhichun Zhao; Xiaofeng Li; Chunyue Liu; Patricia Dale (Wetlands, 2009)

Characterization of the TaAIDFa gene encoding a CRT/DRE-binding factor responsive to drought, high-salt, and cold stress in wheat - Zhao-Shi Xu; Zhi-Yong Ni; Li Liu; Li-Na Nie; Lian-Cheng Li; Ming Chen; You-Zhi Ma (Molecular Genetics and Genomics, 2008)

Effects of Water-Borne Copper on Digestive and Metabolic Enzymes of the Giant Freshwater Prawn Macrobrachium rosenbergii - Na Li; Yunlong Zhao; Jian Yang (Archives of Environmental Contamination and Toxicology, 2008)

Rapid and quantitative detection of p38 kinase pathway in mouse blood monocyte - Jingyong Zhao; Glenn Evans; Weiming Li; Lisa Green; Shaoyou Chu; Phil Marder; Songqing Na (In Vitro Cellular & Developmental Biology - Animal, 2008)

Effects of Water-borne Copper on the Y-organ and Content of 20-hydroxyecdysone in Eriocheir sinensis - Zhi-biao Yang; Yun-long Zhao; Na Li; Jian Yang; Xiu-guo Hua (Archives of Environmental Contamination and Toxicology, 2008)

A new linearly-combined bi-exponential model for kinetic analysis of the isometric relaxation process of Bufo gastrocnemius under electric stimulation in vitro - Rui Guo; Sheng-bing Li; Li-na Zhao; Yun-sheng Zhao; Wei Lu; Pei Yuan; Ping Deng; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2007)

Overexpression of glycerol-3-phosphate acyltransferase gene improves chilling tolerance in tomato - Na Sui; Meng Li; Shi-Jie Zhao; Feng Li; Hui Liang; Qing-Wei Meng (Planta, 2007)

Long-Term Toxicity Effects of Cadmium and Lead on Bufo raddei Tadpoles - Yingmei Zhang; Dejun Huang; Dongqin Zhao; Jing Long; Gang Song; An’na Li (Bulletin of Environmental Contamination and Toxicology, 2007)

Optimization of covalent immobilization of pectinase on sodium alginate support - Tuoping Li; Na Wang; Suhong Li; Qiancheng Zhao; Mei Guo; Cheyun Zhang (Biotechnology Letters, 2007)

Effect of Waterborne Copper on the Microstructures of Gill and Hepatopancreas in Eriocheir sinensis and Its Induction of Metallothionein Synthesis - Zhi-Biao Yang; Yun-Long Zhao; Na Li; Jian Yang (Archives of Environmental Contamination and Toxicology, 2007)

Impact of Waterborne Copper on the Structure of Gills and Hepatopancreas and Its Impact on the Content of Metallothionein in Juvenile Giant Freshwater Prawn Macrobrachium rosenbergii (Crustacea: Decapoda) - Na Li; Yunlong Zhao; Jian Yang (Archives of Environmental Contamination and Toxicology, 2007)

Evaluation of a kinetic uricase method for serum uric acid assay by predicting background absorbance of uricase reaction solution with an integrated method - Fei Liao; Yun-sheng Zhao; Li-na Zhao; Jia Tao; Xiao-yun Zhu; Lan Liu (Journal of Zhejiang University-SCIENCE B, 2006)